Secondary battery, positive electrode active material, and electric device

By using orientation secondary particles in the positive electrode active material of lithium-ion batteries, the internal structure and composition of the particles are controlled, and the shortcomings in lithium-ion batteries in terms of energy density, kinetic performance and cycle life are solved, and higher battery performance is achieved.

CN119833708AActive Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410927544.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-04-15
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in energy density, dynamic performance and cycle life, and it is difficult to meet the range and dynamic performance needs of new energy vehicles.

Method used

Oriented secondary particles including a plurality of primary particle agglomerates are used as the positive electrode active material. By controlling the angle α1 formed by the longest axis of the primary particle and the longitudinal direction and its number of F1 in the secondary particles, the electrolyte infiltration and active ion deintercalation path are adjusted to improve the energy density and cycle life of the battery.

Benefits of technology

Effectively inhibit the penetration of electrolyte into the grain boundaries of secondary particles, reduce side reactions, improve the actual capacity and cycle life of the positive electrode active material, and improve the energy density and kinetic performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833708A_ABST
    Figure CN119833708A_ABST
Patent Text Reader

Abstract

The invention relates to a secondary battery, a positive electrode active material, and a power device. The secondary battery comprises a positive pole piece, the positive pole piece comprises a positive active material, the positive active material comprises secondary particles, and the secondary particles are agglomerated particles comprising a plurality of primary particles; the primary particles comprise a positive electrode active material; in any secondary particle, the direction of the center of the secondary particle towards the surface is recorded as the X direction; the X direction penetrating through the center of any one primary particle is marked as the longitudinal direction; in any one primary particle, the longest axis of the primary particle is recorded as an a axis; the secondary particles comprise oriented secondary particles; in the oriented secondary particles, based on the total number of the primary particles in the oriented secondary particles, the proportion of the number of the primary particles in the oriented secondary particles, in which an included angle alpha 1 is formed between the a axis and the longitudinal direction, is F1, 15 degrees < = alpha < = 45 degrees, and F1 > = 60%. The secondary battery has high energy density, good dynamic performance and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and further to a secondary battery, a positive electrode active material and an electrical device. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] In recent years, with the development of secondary battery technology, secondary batteries represented by lithium-ion batteries have been widely used in many fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. They are also widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations. Among them, lithium-ion batteries occupy an important position in new energy vehicles. In order to meet the requirements for the cruising range, dynamic performance and service life of new energy vehicles, it is necessary to comprehensively improve the energy density, dynamic performance and cycle life of lithium-ion batteries. Summary of the invention

[0004] In view of the above problems, the present application provides a secondary battery, a positive electrode active material and an electric device. The secondary battery has high energy density, good kinetic performance and long cycle life.

[0005] In a first aspect, the present application provides a secondary battery, which includes a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode active material, wherein the positive electrode active material includes secondary particles, wherein the secondary particles are aggregates including a plurality of primary particles; and the primary particles include a positive electrode active material;

[0006] In any of the secondary particles, the direction from the center of the secondary particle toward the surface is recorded as the X direction; the X direction passing through the center of any of the primary particles is recorded as the longitudinal direction; in any of the primary particles, the longest axis of the primary particle is recorded as the a-axis;

[0007] The secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, wherein 15°≤α1≤45°, and F1≥60%.

[0008] The positive electrode active material includes oriented secondary particles, and the oriented secondary particles include a certain number of primary particles whose a-axis forms a certain angle α1 with the corresponding longitudinal direction. On the one hand, by controlling the proportion F1 of the number of primary particles with the aforementioned angle α1 in the oriented secondary particles to be within the aforementioned range, it is beneficial to inhibit the electrolyte from penetrating into the grain boundaries of the secondary particles, and to inhibit the side reactions between the electrolyte and the surface of the positive electrode active material, which can improve the actual gram capacity and cycle life of the positive electrode active material; on the other hand, by controlling the angle α1 within the aforementioned angle range, a shorter active ion deintercalation path can be achieved, which is beneficial to promote the rapid deintercalation of active ions in the positive electrode active material during the charge and discharge process, which can improve the actual energy density of the secondary battery and enable the secondary battery to have good kinetic performance.

[0009] In some embodiments, the angle α1 is obtained as follows: in a cross section passing through the center of the oriented secondary particle, the direction from the center of the oriented secondary particle toward the surface of the oriented secondary particle is taken as the X direction; the X direction passing through the center of the cross section of the primary particle is taken as the longitudinal direction corresponding to the primary particle; the longest axis in the cross section of the primary particle is recorded as the a-axis; and the angle α1 is obtained based on the angle formed by the a-axis and the corresponding longitudinal direction.

[0010] The parameter α1 can be statistically analyzed using a cross-sectional view passing through the center of the oriented secondary particle.

[0011] In some embodiments, F1 ≥ 64%.

[0012] By regulating the proportion (F1) of the primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles within the aforementioned range, on the one hand, it is beneficial to more effectively inhibit the electrolyte from penetrating into the grain boundaries of the secondary particles, thereby more effectively inhibiting the side reactions between the electrolyte and the surface of the positive electrode active material, and better improving the actual gram capacity and cycle life of the positive electrode active material; on the other hand, it is more beneficial to provide a shorter active ion deintercalation path, thereby more beneficial to improving the actual energy density and good kinetic performance of the secondary battery.

[0013] In some embodiments, the proportion of the oriented secondary particles in the secondary particles is recorded as P2, and P2≥60%.

[0014] In some embodiments, P2 ≥ 75%.

[0015] By controlling the proportion of oriented secondary particles in the secondary particles (P2) within the aforementioned range, it is beneficial to more significantly exert the comprehensive improvement effect of the oriented secondary particles on the high energy density, kinetic performance and long cycle life of secondary batteries.

[0016] In some embodiments, the length of the primary particle along the longitudinal direction is recorded as L, the length of the primary particle perpendicular to the longitudinal direction is recorded as W, and the ratio of L to W in the primary particle is recorded as R. L / W ;

[0017] In the oriented secondary particles, the R L / W Less than or equal to 4.

[0018] By adjusting the angle α1 between the a-axis of the primary particle and the corresponding longitudinal direction, the length ratio R of the primary particle in the longitudinal direction and the transverse direction (the transverse direction is the direction perpendicular to the longitudinal direction) can be adjusted. L / W , further, by L / W Adjustment within the aforementioned range is beneficial for denser stacking of the primary particles in the radial direction (X direction) of the oriented secondary particles, thereby being more beneficial for improving the energy density of the battery.

[0019] In some embodiments, the L value, the W value and the R L / W The value is obtained as follows: in a cross section passing through the center of the oriented secondary particle, the direction from the center of the oriented secondary particle toward the surface of the oriented secondary particle is the X direction; the X direction passing through the center of the cross section of the primary particle is the longitudinal direction corresponding to the primary particle; the L value is obtained according to the length value of the primary particle along the corresponding longitudinal direction, the W value is obtained according to the length value of the primary particle along the direction perpendicular to the corresponding longitudinal direction, and the R value is obtained according to the ratio obtained by dividing the L value by the W value. L / W value.

[0020] The above parameters L, W and R can be measured by using a cross-sectional view through the center of the oriented secondary particle. L / W Perform statistical analysis.

[0021] In some embodiments, the positive electrode active material satisfies at least one of the following characteristics:

[0022] In the oriented secondary particles, the R L / W Satisfy 0 <R L / W ≤4;

[0023] In the oriented secondary particles, the R L / W The average value is 1.5 to 2.5.

[0024] In some embodiments, the positive electrode active material satisfies at least one of the following characteristics:

[0025] In the oriented secondary particles, the R L / W Satisfy 0.95≤R L / W ≤4;

[0026] In the oriented secondary particles, the R L / W The average value is 1.5~2.0.

[0027] By adjusting the R of the primary particles in the oriented secondary particles L / W Value range and R L / W When one or two parameters in the average value are within the aforementioned range, the orientation and orientation distribution characteristics of the primary particles can be regulated, and the inhibition of electrolyte penetration and the reversible deintercalation efficiency of active ions can be better taken into account, which is conducive to better taking into account high energy density, cycle performance and good kinetic performance.

[0028] In some embodiments, the distance from the center to the surface of the oriented secondary particle is recorded as R; the portion from the center of the oriented secondary particle to the position 2 / 3R from the center is recorded as the inner layer, and the portion from the position 2 / 3R from the center to the surface of the oriented secondary particle is recorded as the outer layer;

[0029] In the oriented secondary particles, the R L / W The average value is recorded as R MI , the outer layer R L / W The average value is recorded as R MO , where R MI <R MO .

[0030] In the case where the primary particles form the aforementioned angle α1, by further controlling R MI <R MO This is beneficial for faster deintercalation of active ions located in the outer layer and outer surface of the secondary particles, and is more beneficial for improving the kinetic performance of the positive electrode active materials and batteries.

[0031] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0032] In the oriented secondary particles, R MI <1.8, R MO ≥1.8;

[0033] In the oriented secondary particles, the outer layer R L / W Satisfy 1.2≤R L / W ≤4, the inner layer R L / W Satisfy 0.95≤R L / W ≤2.8.

[0034] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0035] In the oriented secondary particles, 1.3≤RMI <1.8, 1.8≤R MO ≤2.3;

[0036] In the oriented secondary particles, at least 80% of the primary particles in the outer layer have R L / W Satisfy 1.4≤R L / W ≤4, at least 80% of the primary particles in the inner layer have R L / W Satisfy 0.95≤R L / W ≤2.0.

[0037] By controlling the inner layer R L / W Value, inner layer R L / W Average value (R MI ), outer layer R L / W Value and outer R L / W Average value (R MO ) has the aforementioned combination mode, which can better control the orientation distribution changes of the primary particles in the inner layer and the outer layer, which is beneficial to better improve the reversible deintercalation efficiency of the active ions of the outer layer primary particles, and can also take into account the inhibition of electrolyte infiltration, which is more conducive to taking into account good cycle performance and kinetic performance.

[0038] In some embodiments, in the oriented secondary particles, the R L / W The value increases from the center of the oriented secondary particle to the surface of the oriented secondary particle.

[0039] By controlling the R L / W Increasing from the center to the surface can better control the orientation distribution changes of the primary particles in the oriented secondary particles, which is beneficial to better improve the reversible deintercalation efficiency of the active ions of the outer primary particles, and can also take into account the inhibition of electrolyte penetration, which is more conducive to taking into account good cycle performance and kinetic performance.

[0040] In some embodiments, the number of primary particles whose a-axis in the oriented secondary particles forms an angle α1 with the longitudinal direction is counted, and the anisotropic index of the angle α1 is recorded as I α1 , then 0.4≤I α1 ≤2.5;

[0041] Wherein, in the cross section passing through the center of the oriented secondary particle, the angle α1 that the a-axis deviates from the corresponding longitudinal direction in the clockwise direction is recorded as a positive angle, and the angle α1 that the a-axis deviates from the corresponding longitudinal direction in the counterclockwise direction is recorded as a negative angle, I α1 It is the ratio of the number of positive angles to the number of negative angles.

[0042] In some embodiments, 0.5≤I α1 ≤2.0.

[0043] The aforementioned parameter I can be used α1 To further reflect the distribution of the orientation direction of the primary particles with an angle α1 in the oriented secondary particles, α1 By controlling within the aforementioned range, the primary particles forming the angle α1 can have a relatively disordered orientation, which is more conducive to inhibiting the electrolyte from penetrating into the grain boundaries of the secondary particles and is more conducive to improving the actual gram capacity and cycle life of the positive electrode active material.

[0044] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0045] The positive electrode active material D v 50: 8μm~11μm;

[0046] The diameter of at least 80% of the primary particles in the oriented secondary particles is in the range of 100 nm to 1600 nm, wherein the diameter of the primary particles refers to the maximum length of the primary particles in each direction;

[0047] The particle size distribution parameter SPAN of the positive electrode active material conforms to the following formula: SPAN = (D v 90-D v 10) / D v 50, among which, 1.1≤SPAN≤1.4.

[0048] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0049] The positive electrode active material D v 50: 9μm~10μm;

[0050] The diameter of at least 80% of the primary particles in the oriented secondary particles is within the range of 400nm to 1500nm;

[0051] The SPAN of the positive electrode active material satisfies: 1.2≤SPAN≤1.3.

[0052] By adjusting the D v Within the aforementioned range, the particles in the positive electrode active material can have a more suitable particle size distribution, thereby having a more suitable specific surface area, which is beneficial for both suppressing side reactions and having a shorter active ion transmission distance, so that the secondary battery has both good cycle performance and kinetic performance.

[0053] By adjusting the diameter of the primary particles in the oriented secondary particles within the aforementioned range, it is beneficial to control the active crystal surface ratio of the primary particles, so that the lithium ion insertion and extraction kinetics of the primary particles can be further improved.

[0054] By adjusting the particle size distribution parameter SPAN of the positive electrode active material within the aforementioned range, it is beneficial to make the large particles and small particles in the positive electrode active material have appropriate volume proportions, so that the positive electrode active material has a high powder compaction density while having a high capacity, which is beneficial to maximizing the volume energy density of the positive electrode side. By designing the size of the particles, the polycrystalline material formed can increase the volume energy density of the positive electrode material.

[0055] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0056] The positive electrode active material D v 90Satisfy: 15μm≤D v 90≤18μm;

[0057] The positive electrode active material D v 10: 4μm≤D v 10≤6μm;

[0058] The positive electrode active material D m 10 Satisfied: D n 10≥2μm.

[0059] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0060] The positive electrode active material D v 90 satisfies: 16μm≤D v 90≤17μm;

[0061] The positive electrode active material D v 10: 4.5μm≤D v 10≤5.5μm.

[0062] By controlling the D v 90 Within the aforementioned range, it is beneficial to control the volume ratio of large particles in the material, to control the specific surface area, and to inhibit side reactions.

[0063] By controlling the D v 10 Within the aforementioned range, it is beneficial to control the appropriate volume ratio of small particles in the material and to improve the compaction density of the material.

[0064] By controlling the D n10 Within the aforementioned range, the number of small particles in the material can be controlled within a more appropriate range, which is beneficial for controlling a more appropriate specific surface area, thereby increasing the storage life of the battery.

[0065] In some embodiments, in the aligned secondary particles, the positive electrode active material includes a layered lithium ion active material.

[0066] In some embodiments, in the aligned secondary particles, the positive electrode active material includes a lithium-containing nickel composite oxide.

[0067] By introducing lithium-nickel composite oxide into the positive electrode active material of the oriented secondary particles, the introduction of nickel element is beneficial to improving the energy density of the positive electrode active material, and is also beneficial to improving the power performance of the battery.

[0068] In some embodiments, the molar ratio of nickel element to oxygen element in the lithium-containing nickel composite oxide is recorded as Q Ni / O , where 0.3≤Q Ni / O ≤0.5.

[0069] The molar ratio (Q Ni / O ) is controlled within the aforementioned range, the positive electrode active material can have a high nickel content, which is more conducive to improving the energy density of the positive electrode active material.

[0070] In some embodiments, the oriented secondary particles satisfy one or more of the following characteristics:

[0071] In the oriented secondary particles, 0.4≤Q Ni / O ≤0.5;

[0072] The lithium-containing nickel composite oxide contains at least one of a cobalt (Co) element and an M element, wherein the M element is at least one of a Mn element and an Al element;

[0073] The lithium-nickel composite oxide contains a doping element, Q Ni / O <0.5, the doping element includes at least one element selected from Zr, Al, B, Sr and Ca;

[0074] At least a portion of the primary particles include a particle body and a coating layer located at least a portion of the surface of the particle body, the particle body includes a lithium-nickel composite oxide, and the coating layer includes at least one element of Zr, Al, B, Sr and Ca.

[0075] By adding Q Ni / O When controlled within the aforementioned range, the lithium-nickel composite oxide has a high nickel content and can significantly improve the energy density of the positive electrode active material.

[0076] Introducing cobalt (Co) element into lithium-nickel composite oxide is beneficial to stabilizing the material structure and improving the cycle and rate performance of the positive electrode active material.

[0077] Introducing manganese (Mn) element into lithium-nickel composite oxide is beneficial to reducing cost and improving structural stability of the material.

[0078] Introducing aluminum (Al) elements into lithium-nickel composite oxides can help improve the cycle stability of the material.

[0079] By modifying the lithium-nickel composite oxide by one or more of the above-mentioned doping and the above-mentioned coating, one or more of the following aspects can be achieved: enhancing the stability of the material, improving the energy density of the material, and improving the cycle life. For example, the structure of the lithium-nickel composite oxide can be stabilized by bulk doping. For example, a fast ion conductor coating material can be provided on the surface of the lithium-nickel composite oxide to improve the energy density and cycle life of the material.

[0080] In some embodiments, in the oriented secondary particles, 0.3≤Q Ni / O ≤0.5; further, in the oriented secondary particles, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and any modified form of the foregoing substances, wherein the modified form includes one or more of doping modification and coating modification, the doping element used for the doping modification includes at least one of Zr, Al, B, Sr and Ca, and the coating element used for the coating modification includes at least one of Zr, Al, B, Sr and Ca;

[0081] The molar ratio R of the nickel element to the oxygen element in the positive electrode active material is Ni / O Satisfy 0.4≤R Ni / O ≤0.5.

[0082] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0083] The positive electrode active material D v 50 is 8μm~11μm, and can be 9μm~10μm;

[0084] The diameter of at least 80% of the primary particles in the oriented secondary particles is in the range of 100nm to 1600nm, and can be in the range of 400nm to 1500nm;

[0085] The particle size distribution parameter SPAN of the positive electrode active material conforms to the following formula: SPAN = (D v 90-D v 10) / Dv 50, wherein 1.1≤SPAN≤1.4, optionally, 1.2≤SPAN≤1.3.

[0086] The positive electrode active material of the oriented secondary particles can be provided with a ternary positive electrode active material with a high nickel content and its modified material. The modified form can include one or more of doping modification and coating modification, which can be used to obtain a ternary positive electrode active material with high energy density and long life. The structure of the ternary positive electrode active material can be stabilized by bulk phase doping, and the energy density and cycle life of the material can be improved by providing a fast ion conductor coating material on the surface of the ternary positive electrode active material. Combined with the regulation of the angle α1 and F1, the orientation and distribution of the primary particles in the secondary particles of the positive electrode active material can be regulated, and the balance between inhibiting the electrolyte from penetrating the interior and optimizing the distance of the lithium ion transmission path can be taken into account, thereby improving the mass energy density of the material and the lithium ion diffusion kinetics. Furthermore, by controlling the D of the positive electrode active material v 50. The diameter of the primary particles in the oriented secondary particles and one or more parameters in the particle size distribution parameter SPAN of the positive electrode active material are within the aforementioned range, and the aforementioned related advantages can be further combined. For example, by adjusting the particle size distribution parameter SPAN of the positive electrode active material within the aforementioned range, it is beneficial to make the large particles and small particles in the positive electrode active material have a suitable volume proportion, respectively, which can further improve the powder compaction density of the material and the volume energy density of the positive electrode sheet. By designing the secondary particles to match large and small particles, the polycrystalline material formed can increase the volume energy density of the positive electrode material. Furthermore, the doping and coating modification methods can be combined to improve the bulk structure and surface stability of the material to achieve a longer cycle life.

[0087] In some embodiments, in the oriented secondary particles, the average L value of the inner layer is less than 700 nm, and the average L value of the outer layer is greater than or equal to 720 nm;

[0088] Among them, the length value of the primary particle along the longitudinal direction is recorded as L, and the distance from the center to the surface of the oriented secondary particle is recorded as R; the part from the center of the oriented secondary particle to the position 2 / 3R from the center is recorded as the inner layer, and the part from the position 2 / 3R from the center to the surface of the oriented secondary particle is recorded as the outer layer.

[0089] In some embodiments, in the oriented secondary particles, the average L value of the inner layer is less than or equal to 660 nm, and the average L value of the outer layer is greater than or equal to 750 nm.

[0090] For the positive electrode active material in the oriented secondary particles, including the positive electrode active material containing lithium nickel composite oxide, by controlling the L average value of the inner layer and the outer layer in the oriented secondary particles within the aforementioned range, the outer layer can have a faster reversible deintercalation efficiency of the active ions, and the inner layer can have a larger angle to better inhibit the electrolyte from penetrating into the grain boundary, which is more conducive to comprehensively improving the actual energy density, cycle performance and kinetic performance of the battery.

[0091] In some embodiments, the secondary battery further includes a negative electrode sheet, a separator and an electrolyte, and the separator is located between the positive electrode sheet and the negative electrode sheet.

[0092] In some embodiments, the secondary battery is a lithium ion secondary battery.

[0093] In a second aspect of the present application, a positive electrode active material is provided.

[0094] In some embodiments, the positive electrode active material includes secondary particles, the secondary particles are aggregates including primary particles; the primary particles include a positive electrode active material;

[0095] In any of the secondary particles, the direction from the center of the secondary particle toward the surface is recorded as the X direction; the X direction passing through the center of any of the primary particles is recorded as the longitudinal direction; in any of the primary particles, the longest axis of the primary particle is recorded as the a-axis;

[0096] The secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, wherein 15°≤α1≤45°, and F1≥60%.

[0097] The positive electrode sheet prepared using the above-mentioned positive electrode active material can be used to prepare a secondary battery with high energy density, good kinetic performance and long cycle life. By using the orientation angle and quantity ratio of the primary particles included in the oriented secondary particles in the positive electrode active material, it is possible to inhibit the electrolyte from penetrating into the grain boundary of the secondary particles, which is beneficial to inhibit the side reaction between the electrolyte and the surface of the positive electrode active material, and can improve the actual gram capacity and cycle life of the positive electrode active material. It can also achieve a shorter active ion deintercalation path, which is beneficial to promote the rapid deintercalation of active ions during the charge and discharge process, which can improve the actual energy density of the secondary battery and make the secondary battery have good kinetic performance.

[0098] In some embodiments, the positive electrode active material in the secondary battery described in the first aspect of the present application is provided.

[0099] In a third aspect of the present application, an electrical device is provided, which includes the secondary battery described in the first aspect of the present application and at least one of the positive electrode active materials described in the second aspect of the present application.

[0100] Details of one or more implementations or embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0101] In order to better describe and illustrate the embodiments, examples or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments, examples or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0102] Figure 1 Schematic diagram of relevant parameters of oriented secondary particles in one embodiment of the present application, wherein only the cross-section of part of the primary particles at the two-dimensional cross-section of the oriented secondary particles is shown.

[0103] Figure 2 This is the experimental result of the cross-sectional view of the oriented secondary particles in one embodiment of the present application.

[0104] Figure 3 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0105] Figure 4 for Figure 3 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0106] Figure 5 It is a schematic diagram of a battery module according to one embodiment of the present application.

[0107] Figure 6 A schematic diagram of a battery pack according to an embodiment of the present application.

[0108] Figure 7 for Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0109] Figure 8 FIG. 1 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0110] Description of reference numerals:

[0111] 52, electrode assembly; 1, battery pack; 2, upper box; 3, lower box; 4, battery module; 5, battery cell; 51, shell; 53, cover plate; 6, electrical device. DETAILED DESCRIPTION

[0112] Below, some embodiments and examples of the secondary battery, positive electrode active material and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0113] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0114] In the present application, "multiple", "multiple", "multiple", "several", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to (≥, greater than or equal to) two. It is understood that when "any number" of items are involved, it refers to any suitable combination of multiple items, that is, the combination of "any number" of items is performed in a manner that does not conflict and can implement the present application.

[0115] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0116] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0117] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed in sequence, or can be performed randomly, and can preferably be performed in sequence. For example, method M includes steps (a) and (b), indicating that method M may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For another example, method M may also include step (c), indicating that step (c) can be added to method M in any order, for example, method M may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0118] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" or "A is selected from a1, a2 and a3", and the feature or solution of "A includes not only a1, a2 and a3, but also other members".

[0119] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0120] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel solutions of "yes" or "no". If there are multiple "optional" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent. Unless otherwise specified, the descriptions of "optionally include", "optionally include", etc. in this application, taking "optionally include" as an example, mean "may include or not include".

[0121] In the present application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a group consisting of A, B, and "a combination of A and B". Among them, "comprising A and / or B" can mean "comprising A, comprising B, and comprising A and B", and can also mean "comprising A, comprising B, or comprising A and B", which can be properly understood according to the sentence in which it is located.

[0122] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.

[0123] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the technical solution that can implement the present application.

[0124] Herein, "preferred", "better", "more preferred", "suitable", "better", and "preferable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0125] In the present application, “further”, “furthermore”, “particularly”, “for example”, “such as”, “example”, “for example”, etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of the present application.

[0126] In the present application, the terms "first", "second", "third", etc. in "the first aspect", "the second aspect", "the third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0127] In the present application, the term "room temperature" generally refers to 4°C to 35°C, and may refer to 20°C±5°C. In some embodiments of the present application, room temperature refers to 20°C to 30°C.

[0128] In this application, when the unit of a data range is mentioned, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3~5h or 3-5h both mean that the units of the left endpoint "3" and the right endpoint "5" are both h (hours), which have the same meaning as 3h~5h. In addition, similar descriptions of other parameters such as temperature and size are also understood in the same way.

[0129] The weight or mass of the relevant components mentioned in the embodiments or examples of the present application can not only refer to the content of each component, but also represent the proportional relationship of the weight or mass between the components. Therefore, as long as the content of the relevant components of the embodiments or examples of the present application is proportionally enlarged or reduced, it is within the scope described in the present application. Further, the mass involved in the embodiments or examples of the present application can be a mass unit known in the chemical industry such as microgram (μg), milligram (mg), gram (g), kilogram (kg). If not otherwise specified, the mass ratio is equal to the corresponding weight ratio, such as the mass of substance A is m1, the weight is W1, the mass of substance B is m2, and the weight is W2, then the mass ratio m1 / m2 of the two is numerically equal to the corresponding weight ratio W1 / W2.

[0130] In the present application, unless otherwise specified, wt% represents weight percentage by weight, which is numerically equal to the corresponding mass percentage by mass.

[0131] In this application, "greater than or equal to", "greater than or equal to" and "≥" have the same meaning and can be used interchangeably; "less than or equal to", "less than or equal to" and "≤" have the same meaning and can be used interchangeably; "greater than" can be equivalently expressed as ">", and "less than" can be equivalently expressed as "<". In this application, unless otherwise specified, "greater than or equal to" and "≥" can be regarded as providing two solutions of "greater than" and "equal to". In this application, unless otherwise specified, "less than or equal to" and "≤" can be regarded as providing two solutions of "less than" and "equal to".

[0132] In the present application, exemplary descriptions such as "in some implementation modes (or examples)" and "in one implementation mode (or example)" may include but are not limited to the following meanings: these solutions may be combined with other solutions in a suitable manner to form new technical solutions.

[0133] A common form of positive electrode active material is polycrystalline material, in which case the secondary particles are composed of multiple primary particles. Taking lithium ion active materials as an example, in the secondary particles usually obtained, the longest axis (a-axis) of the primary particles is basically consistent with the direction from the center to the surface of the secondary particles. At this time, the transmission distance of lithium ions can be shortened to improve the dynamics of the positive electrode active material during lithium ion deintercalation. However, due to the overly regular orientation of the primary particles, there are obvious through-channels between the primary particles, making it easy for the electrolyte to penetrate into the secondary particles, causing more serious interface side reactions, resulting in reduced cycle performance and actual gram capacity of the positive electrode active material, and thus deteriorating the cycle life of the material.

[0134] In view of this, the present application provides a secondary battery, a positive electrode active material and an electric device. The secondary battery has high energy density, good kinetic performance and long cycle life.

[0135] In some embodiments, a secondary battery includes a positive electrode plate, the positive electrode plate includes a positive electrode active material, the positive electrode active material includes secondary particles, and the secondary particles are agglomerates including multiple primary particles; in any primary particle, the longest axis of the primary particle is recorded as the a-axis; the X direction passing through the center of any primary particle is recorded as the longitudinal direction; in any secondary particle, the direction from the center of the secondary particle toward the surface is recorded as the X direction; the secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, 15°≤α1≤45°, F1≥60%.

[0136] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0137] In the present application, unless otherwise specified, the electrode plate may be a positive electrode plate or a negative electrode plate, and the "active material" in the electrode plate refers to a material that can reversibly embed and remove active ions. Unless otherwise specified, "negative electrode active material" refers to a material used for negative electrode plates that can reversibly embed and remove active ions; "positive electrode active material" refers to a material used for positive electrode plates that can reversibly remove and embed active ions. When a battery cell or a secondary battery is charged, the active ions are removed from the positive electrode and embedded in the negative electrode through the electrolyte; and when the battery cell or the secondary battery is discharged, the active ions are removed from the negative electrode and embedded in the positive electrode. The active ions are not particularly limited. In some embodiments, the active ions may include lithium ions. Non-limitingly, the active ions may be lithium ions, in which case the battery cell is a lithium-ion battery cell and the secondary battery is a lithium-ion secondary battery.

[0138] In the present application, "electrode plate" and "electrode electrode plate" have the same meaning and can be used interchangeably; "electrode active material" and "active material" have the same meaning and can be used interchangeably.

[0139] In the present application, unless otherwise specified, the "electrode active material layer" includes at least one of the positive electrode active material layer of the positive electrode sheet and the negative electrode active material layer of the negative electrode sheet. Depending on the detailed circumstances, the electrode active material layer may refer to the positive electrode active material layer or the negative electrode active material layer. It is understood that the positive electrode active material layer contains positive electrode active substances, and the negative electrode active material layer contains negative electrode active substances. In the present application, the "electrode active material layer" may also be abbreviated as the "active material layer".

[0140] In the present application, unless otherwise specified, "separation membrane" and "diaphragm" have the same meaning and can be used interchangeably.

[0141] It can be understood that both “primary particles” and “secondary particles” are particles including a positive electrode active material.

[0142] In the present application, "primary particles" and "secondary particles" are terms well known in the art. "Primary particles" refer to single crystals or single crystal-like grains. "Secondary particles" refer to particles in an agglomerated state formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be easily distinguished by experimental means, for example, by using SEM images taken by a scanning electron microscope (SEM), but are not limited thereto.

[0143] In a first aspect of the present application, a secondary battery is provided, which includes a positive electrode plate, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes oriented secondary particles.

[0144] In some embodiments, a secondary battery is provided, which includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes secondary particles, the secondary particles are agglomerated particles including a plurality of primary particles; the primary particles include a positive electrode active material;

[0145] In any secondary particle, the direction from the center of the secondary particle to the surface is recorded as the X direction; the X direction passing through the center of any primary particle is recorded as the longitudinal direction; in any primary particle, the longest axis of the primary particle is recorded as the a-axis;

[0146] The secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, where 15°≤α1≤45°, and F1≥60%.

[0147] In this application, unless otherwise specified, "X direction" refers to the direction from the center of the secondary particle toward the surface. It can be understood that different positions on the secondary particle surface from the center of the secondary particle correspond to different X directions; each position on the secondary particle surface corresponds to its corresponding X direction.

[0148] In the present application, unless otherwise specified, "longitudinal direction" refers to a direction passing through the center of a secondary particle and the center of a primary particle at the same time. It can be understood that different primary particles correspond to different longitudinal directions, and each primary particle corresponds to its corresponding longitudinal direction.

[0149] In the present application, unless otherwise specified, the "a-axis" of a primary particle refers to the longest axis of the primary particle in all directions. Generally, the longest axis in a two-dimensional cross section of the primary particle can be used as the test result of the a-axis length.

[0150] In the present application, unless otherwise specified, the percentage of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1.

[0151] In the present application, unless otherwise specified, "oriented secondary particles" refer to a certain number of primary particles having the following characteristics: the a-axis of the primary particle forms a certain angle with the corresponding longitudinal direction. Unless otherwise specified, the angle formed by the a-axis of the primary particle and the corresponding longitudinal direction is recorded as "α1", which can be called "angle α1". Unless otherwise specified, the percentage of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as "F1". In the present application, generally, when a secondary particle satisfies 15°≤α1≤45° and F1≥60%, it is judged to be an oriented secondary particle.

[0152] The positive electrode active material includes oriented secondary particles, and the oriented secondary particles include a certain number of primary particles whose a-axis forms a certain angle α1 with the corresponding longitudinal direction. On the one hand, by controlling the proportion F1 of the number of primary particles with the aforementioned angle α1 in the oriented secondary particles to be within the aforementioned range, it is beneficial to inhibit the electrolyte from penetrating into the grain boundaries of the secondary particles, and to inhibit the side reactions between the electrolyte and the surface of the positive electrode active material, which can improve the actual gram capacity and cycle life of the positive electrode active material; on the other hand, by controlling the angle α1 within the aforementioned angle range, a shorter active ion deintercalation path can be achieved, which is beneficial to promote the rapid deintercalation of active ions in the positive electrode active material during the charge and discharge process, which can improve the actual energy density of the secondary battery and enable the secondary battery to have good kinetic performance.

[0153] In some embodiments of the present application, the angle α1 can be obtained in the following manner: in a cross-section passing through the center of an oriented secondary particle, the direction from the center of the oriented secondary particle toward the surface of the oriented secondary particle is taken as the X direction; the X direction passing through the center of the cross-section of the primary particle is taken as the longitudinal direction corresponding to the primary particle; the longest axis in the cross-section of the primary particle is recorded as the a-axis; and the angle α1 is obtained based on the angle formed by the a-axis and the corresponding longitudinal direction.

[0154] The above parameter α1 can be statistically analyzed using a cross-sectional view passing through the center of the oriented secondary particle. It is understood that in the cross-sectional view passing through the center of the oriented secondary particle, the cross section and cross-sectional profile of the oriented secondary particle can be displayed, and the cross section and cross-sectional profile of the primary particle can also be displayed. Unless otherwise specified, the center of the oriented secondary particle can be determined as follows: based on the cross-sectional profile of the oriented secondary particle, the intersection between the longest axis and the shortest axis in the cross section of the oriented secondary particle is taken as the center of the oriented secondary particle.

[0155] The ion polishing cross-sectional morphology analysis method can be used to perform statistical analysis on the parameters related to the primary particles in the oriented secondary particles. In a non-limiting manner, the secondary particles can be cut to form a cross section that basically passes through the center of the secondary particles, and a sample with the cut surface is obtained, and further combined with the microscopic morphology observation method, the relevant parameters of the primary particles in the cross-sectional view of the secondary particles are statistically analyzed. In a non-limiting manner, instruments or equipment including but not limited to focused electron beam (FIB) electron microscopes (non-limiting examples such as FEI Scios 2HiVac equipment, etc.), ion cross-sectional polishers (non-limiting examples such as IB-09010 CP argon ion cross-sectional polishers, IB-19500CP ion cross-sectional polishers, etc. of JEOL, Japan) can be used to obtain a cross section that basically passes through the center of the secondary particles. The microscopic morphology observation method may use instruments or equipment including but not limited to scanning electron microscopy (SEM) technology, and non-limitingly, a high-resolution field emission scanning electron microscope may be used; non-limiting examples of SEM instruments include Sigma 300 scanning electron microscope and Apreo 2 SEM field emission scanning electron microscope of ZEISS, Germany. In some embodiments, a cross-sectional view through the center of the secondary particle is obtained by combining ion polishing cross-sectional morphology analysis with scanning electron microscopy (SEM).

[0156] The above method can be used to analyze parameters including but not limited to the following: the a-axis of the primary particle, the angle between the a-axis of the primary particle and the corresponding longitudinal direction (angle α1), the number of primary particles with the a-axis and the longitudinal direction forming an angle α1, the deviation direction of the angle α1 relative to the X direction, and the anisotropic index I of the angle α1. α1 , the length of the primary particle along the longitudinal direction L, the length of the primary particle perpendicular to the longitudinal direction W, the inner layer R L / W Average value (R MI ), the outer R L / W Average value (R MO ) etc. The determination methods of some of the above parameters can be found in Figure 1 The test and analysis method may also be used in the following examples. Figure 1 Only the cross section of a part of the primary particles at the cross section of the oriented secondary particles is shown.

[0157] In some embodiments, the oriented secondary particles are spherical or quasi-spherical. The aspect ratio of "quasi-spherical particles" is close to 1, and non-limiting examples include 0.8 to 1.2. The aspect ratio of quasi-spherical particles refers to the ratio of its longest axis to its shortest axis. Methods known in the art and conventional instruments can be used for testing and analysis.

[0158] In some embodiments, F1≥60%, which may be F1≥64%, or may be any of the following percentages, or may be greater than or equal to any of the following percentages, or may be selected from the interval between any of the following percentages and 100%: 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 80%, 85%, 90%, 95%, etc. In a non-limiting manner, F1 may also be any of the following ranges: 60% to 100%, 70% to 100%, 60% to 90%, 70% to 90%, etc.

[0159] By regulating the proportion (F1) of the primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles within the aforementioned range, on the one hand, it is beneficial to more effectively inhibit the electrolyte from penetrating into the grain boundaries of the secondary particles, thereby more effectively inhibiting the side reactions between the electrolyte and the surface of the positive electrode active material, and better improving the actual gram capacity and cycle life of the positive electrode active material; on the other hand, it is more beneficial to provide a shorter active ion deintercalation path, thereby more beneficial to improving the actual energy density and good kinetic performance of the secondary battery.

[0160] In the present application, unless otherwise specified, the percentage of oriented secondary particles in the secondary particles is recorded as P2.

[0161] In some embodiments, P2≥60%, which may be P2≥70%, which may be P2≥75%, or may be any of the following percentages, or may be greater than or equal to any of the following percentages, or may be selected from the interval consisting of any two of the following percentages, or may be selected from the interval consisting of any of the following percentages and 100%: 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 72%, 75%, 80%, 85%, 90%, 95%, 99%, etc. In a non-limiting manner, P2 may also be any of the following ranges: 60% to 100%, 70% to 100%, 80% to 100%, 90% to 100%, etc.

[0162] By controlling the proportion of oriented secondary particles in the secondary particles (P2) within the aforementioned range, it is beneficial to more significantly exert the comprehensive improvement effect of the oriented secondary particles on the high energy density, kinetic performance and long cycle life of secondary batteries.

[0163] P2 can be obtained by the following method, but is not limited thereto: Based on a randomly selected cross-sectional view including at least 10 secondary particles, and based on the SEM analysis results of the cross-sectional view passing through the center of the secondary particle, determine whether it is an oriented secondary particle. When 15°≤α1≤45°, F1≥60%, it is counted as one oriented secondary particle; when α1 is not within the above range or F1<60%, it is not counted as an oriented secondary particle. Based on the counting results, calculate the percentage of the number of oriented secondary particles.

[0164] In this application, unless otherwise specified, the length of a primary particle along the longitudinal direction is recorded as L, the shortest length perpendicular to the longitudinal direction in a primary particle is recorded as W, and the ratio of L to W in a primary particle is recorded as R. L / W .

[0165] In some embodiments, in the oriented secondary particles, the R L / W Less than or equal to 4.

[0166] By adjusting the angle α1 between the a-axis of the primary particle and the corresponding longitudinal direction, the length ratio R of the primary particle in the longitudinal direction and the transverse direction (the transverse direction is the direction perpendicular to the longitudinal direction) can be adjusted. L / W , further, by L / W Adjustment within the aforementioned range is beneficial for denser stacking of the primary particles in the radial direction (X direction) of the oriented secondary particles, thereby being more beneficial for improving the energy density of the battery.

[0167] In some embodiments, the L value, W value and R L / W The value can be obtained as follows: in a cross section passing through the center of the oriented secondary particle, the direction from the center of the oriented secondary particle toward the surface of the oriented secondary particle is the X direction; the X direction passing through the center of the cross section of the primary particle is the longitudinal direction corresponding to the primary particle; the L value is obtained according to the length value of the primary particle along the corresponding longitudinal direction, the W value is obtained according to the length value of the primary particle along the direction perpendicular to the corresponding longitudinal direction, and the R value is obtained according to the ratio obtained by dividing the L value by the W value. L / W value.

[0168] The above parameters L, W and R can be measured by using a cross-sectional view through the center of the oriented secondary particle. L / W Perform statistical analysis.

[0169] In some embodiments, the positive electrode active material satisfies at least one of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0170] In the oriented secondary particles, the R L / W Satisfy 0 <R L / W ≤4, optionally, 0.95≤RL / W ≤4;

[0171] In the oriented secondary particles, the R L / W The average value is 1.5~2.5, and can be selected as 1.5~2.0.

[0172] In some embodiments, in the oriented secondary particles, the R L / W Satisfy 0 <R L / W ≤4, optionally, 0.95≤R L / W ≤4. Without limitation, the R L / W The average value of can also be any of the following values, or an interval consisting of any two of the following values: 0.95, 0.96, 0.98, 1, 1.0, 1.1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, 2.0, 2.1, 2.2, 2.4, 2.5, 2.6, 2.8, 3, 3.0, 3.2, 3.4, 3.5, 3.6, 3.7, 3.8, 4.0, 4, etc. For example, the R of a primary particle is L / W The average value can also be selected from any of the following ranges: 0.95≤R L / W ≤3.8、0.95≤R L / W ≤3.7、0.98≤R L / W ≤3.67, etc.

[0173] In some embodiments, in the oriented secondary particles, the R L / W The average value of is 1.5 to 2.5, and can be 1.5 to 2.0. In a non-limiting manner, the R L / W The average value can also be any of the following values, or an interval consisting of any two of the following values: 1.5, 1.6, 1.7, 1.8, 1.85, 1.86, 1.9, 2, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, etc.

[0174] By adjusting the R of the primary particles in the oriented secondary particles L / W Value range and R L / W When one or two parameters in the average value are within the aforementioned range, the orientation and orientation distribution characteristics of the primary particles can be regulated, and the inhibition of electrolyte penetration and the reversible deintercalation efficiency of active ions can be better taken into account, which is conducive to better taking into account high energy density, cycle performance and good kinetic performance.

[0175] In the present application, unless otherwise specified, the distance from the center to the surface of the oriented secondary particle is denoted as R; the portion from the center of the oriented secondary particle to the position 2 / 3R from the center is denoted as the inner layer, and the portion from the position 2 / 3R from the center to the surface of the oriented secondary particle is denoted as the outer layer.

[0176] In this application, unless otherwise specified, in the oriented secondary particles, the inner layer R L / W The average value is recorded as R MI , the outer R L / W The average value is recorded as R MO .

[0177] In some embodiments, R MI <R MO .

[0178] In the case where the primary particles form the aforementioned angle α1, by further controlling R MI <R MO This is beneficial for faster deintercalation of active ions located in the outer layer and outer surface of the secondary particles, and is more beneficial for improving the kinetic performance of the positive electrode active materials and batteries.

[0179] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0180] In the oriented secondary particles, R MI <1.8(optionally 1.3≤R MI <1.8), R MO ≥1.8(optional: 1.8≤R MO ≤2.3);

[0181] In the oriented secondary particles, the outer layer R L / W Satisfy 1.2≤R L / W ≤4, inner layer R L / W Satisfy 0.95≤R L / W ≤2.8.

[0182] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0183] In oriented secondary particles, 1.3≤R MI <1.8, 1.8≤R MO ≤2.3;

[0184] In the oriented secondary particles, at least 80% of the primary particles in the outer layer have R L / W Satisfy 1.4≤R L / W ≤4, at least 80% of the primary particles in the inner layer have R L / W Satisfy 0.95≤R L / W ≤2.0.

[0185] In some embodiments, RMI <1.8, optionally, 1.3≤R MI <1.8, further optionally, 1.3≤R MI ≤1.75. Without limitation, R MI It can also be any of the following values, or greater than or equal to any of the following values ​​and less than 1.8, or selected from the interval consisting of any two of the following values: 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, etc. In a non-limiting manner, R MI It can also be selected from any of the following ranges: 1.4≤R MI <1.8, 1.4≤R MI ≤1.75、1.4≤R MI ≤1.6、1.45≤R MI ≤1.55, etc.

[0186] In some embodiments, R MO ≥1.8, optionally, 1.8≤R MO ≤2.3. Without limitation, R MO It can also be any of the following values, or greater than or equal to 1.8 and less than or equal to any of the following values, or selected from an interval consisting of any two of the following values: 1.8, 1.85, 1.9, 1.95, 2, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, etc. In a non-limiting manner, R MO It can also be selected from any of the following ranges: 1.8≤R MO ≤2.2、1.9≤R MO ≤2.1、2.0≤R MO ≤2.1, etc.

[0187] In some embodiments, in the oriented secondary particles, the outer layer R L / W Satisfy 1.2≤R L / W ≤4. Without limitation, the outer layer R L / W It can be any of the following values, or an interval consisting of any two of the following values: 1.2, 1.4, 1.5, 1.6, 1.8, 2.0, 2.5, 3, 3.0, 3.2, 3.4, 3.5, 3.6, 3.7, 3.8, 4, 4.0, etc.

[0188] In some embodiments, in the oriented secondary particles, at least 80% by number of the primary particles in the outer layer have R L / W Satisfy 1.4≤R L / W ≤4. Without limitation, at least 80% of the primary particles in the outer layer have an R L / WIt can be any of the following values, or an interval consisting of any two of the following values: 1.4, 1.5, 1.6, 1.8, 2.0, 2.5, 3, 3.0, 3.2, 3.4, 3.5, 3.6, 3.7, 3.8, 4, 4.0, etc.

[0189] In some embodiments, in the oriented secondary particles, the inner layer R L / W Satisfy 0.95≤R L / W ≤2.8. Without limitation, the R L / W It can be any of the following values, or an interval consisting of any two of the following values: 0.95, 0.96, 0.98, 1, 1.0, 1.1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, 2.0, 2.1, 2.2, 2.4, 2.5, 2.6, 2.8, etc.

[0190] In some embodiments, in the oriented secondary particles, at least 80% of the number of primary particles in the inner layer have R L / W Satisfy 0.95≤R L / W ≤2.0. Without limitation, at least 80% of the primary particles in the inner layer have an R L / W It can be any of the following values, or an interval consisting of any two of the following values: 0.95, 0.96, 0.98, 1, 1.0, 1.1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, 2.0, etc.

[0191] By controlling the inner layer R L / W Value, inner layer R L / W Average value (R MI ), outer layer R L / W Value and outer R L / W Average value (R MO ) has the aforementioned combination mode, which can better control the orientation distribution changes of the primary particles in the inner layer and the outer layer, which is beneficial to better improve the reversible deintercalation efficiency of the active ions of the outer layer primary particles, and can also take into account the inhibition of electrolyte infiltration, which is more conducive to taking into account good cycle performance and kinetic performance.

[0192] In some embodiments, in the oriented secondary particles, the R L / W The value increases from the center of the oriented secondary particle to the surface of the oriented secondary particle.

[0193] By controlling the R L / WIncreasing from the center to the surface can better control the orientation distribution changes of the primary particles in the oriented secondary particles, which is beneficial to better improve the active ion deintercalation efficiency of the outer primary particles, and can also take into account the inhibition of electrolyte penetration, which is more conducive to taking into account good cycle performance and kinetic performance.

[0194] In this application, unless otherwise specified, the number of primary particles whose a-axis in the oriented secondary particles forms an angle α1 with the longitudinal direction is counted, and the anisotropic index of the angle α1 is recorded as I α1 I can be measured in the following way α1 : In the cross section passing through the center of the oriented secondary particle, the angle α1 that the a-axis deviates from the corresponding longitudinal direction in the clockwise direction is recorded as a positive angle, and the angle α1 that the a-axis deviates from the corresponding longitudinal direction in the counterclockwise direction is recorded as a negative angle, I α1 It is the ratio of the number of positive angles to the number of negative angles.

[0195] In some embodiments, 0.4≤I α1 ≤2.5.

[0196] In some embodiments, 0.5≤I α1 ≤2.0.

[0197] Without limitation, I α1 It can be any of the following values, or an interval consisting of any two of the following values: 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1, 1.2, 1.4, 1.6, 1.7, 1.75, 1.8, 2.0, 2, 2.2, 2.4, 2.5, etc. In a non-limiting manner, I α1 Can be any of the following ranges: 1≤I α1 ≤2.5、1.5≤I α1 ≤2.0, etc.

[0198] The aforementioned parameter I can be used α1 To further reflect the distribution of the orientation direction of the primary particles with an angle α1 in the oriented secondary particles, α1 By controlling within the aforementioned range, the primary particles forming the angle α1 can have a relatively disordered orientation, which is more conducive to inhibiting the electrolyte from penetrating into the grain boundaries of the secondary particles and is more conducive to improving the actual gram capacity and cycle life of the positive electrode active material.

[0199] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0200] The D of positive electrode active material v 50 is 8μm~11μm, and can be 9μm~10μm;

[0201] The diameter of the primary particles in the oriented secondary particles is 100nm to 1600nm, and can be 400nm to 1500nm;

[0202] The particle size distribution parameter SPAN of the positive electrode active material conforms to the following formula: SPAN = (D v 90-D v 10) / D v 50, wherein 1.1≤SPAN≤1.4; optionally, 1.2≤SPAN≤1.3.

[0203] In some embodiments, D of the positive electrode active material v 50 is 8 μm to 11 μm, and can be 9 μm to 10 μm. In a non-limiting manner, D of the positive electrode active material v 50 can also be any of the following values ​​or an interval consisting of any two of the following values: 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, etc.

[0204] By adjusting the D v Within the aforementioned range, the particles in the positive electrode active material can have a more suitable particle size distribution, thereby having a more suitable specific surface area, which is beneficial for both suppressing side reactions and having a shorter active ion transmission distance, so that the secondary battery has both good cycle performance and kinetic performance.

[0205] In the context of this application, the volume cumulative distribution particle size D v N (where N represents any value selected from 0 to 100) is used to characterize the particle size of the material, which refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches N%, and the particle size is less than or equal to D v The volume percentage of N is N%. v N can be obtained from the volume cumulative distribution curve of the material particle size. If there is no other explanation, the volume cumulative distribution curve starts from zero from the small particle size side. v 90.D v 50. D v 10 is used as an example for explanation. In this application, unless otherwise specified, D v 90 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 90%. This parameter indicates that the particle size of 90% of the material volume is less than or equal to D v 90, and 10% of the particles by volume are larger than D v 90. In this application, unless otherwise specified, D v50 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. This parameter indicates that the particle size of particles that account for 50% of the volume of the material is less than or equal to D v 50, and 50% of the particles by volume are larger than D v 50. In this application, unless otherwise specified, D v 10 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%.

[0206] D n 10 can be obtained from the number cumulative distribution curve of the material particle size. If there is no other explanation, the number cumulative distribution curve starts from zero from the small particle size side. In this application, if there is no other explanation, D n 10 refers to the particle size corresponding to when the cumulative number distribution percentage of the material reaches 10%.

[0207] Those skilled in the art will understand that v 90.D v 50. D v 10 and D n 10, and can be measured by instruments and methods known in the art. For example, it can be conveniently measured by laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as Mastersizer 2000E laser particle size analyzer and LS-909 laser particle size analyzer (OMEC) of Malvern Instruments Ltd., UK. Further, for equipment models such as Malvern 2000 (MasterSizer 2000) laser particle size analyzer, the standard process GB / T19077-2016 / ISO 13320:2009 can be referred to for testing.

[0208] In some embodiments, the diameter of at least a portion of the primary particles in the oriented secondary particles is in the range of 100 nm to 1600 nm, optionally in the range of 200 nm to 1500 nm, and further optionally in the range of 400 nm to 1500 nm. Without limitation, the diameter of at least a portion of the primary particles in the oriented secondary particles is in the range of any two of the following values: 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, etc. Without limitation, the diameter of at least a portion of the primary particles in the oriented secondary particles is within any of the following ranges: 100nm to 500nm, 200nm to 500nm, 400nm to 1600nm, 400nm to 1500nm, 400nm to 1400nm, 400nm to 1350nm, 400nm to 1200nm, 400nm to 1000nm, 450nm to 1600nm, 450nm to 1500nm, 450nm to 1400nm, 450nm to 1350nm, 450nm to 1200nm, 450nm to 1000nm, etc.

[0209] In some embodiments, at least 80% of the primary particles in the oriented secondary particles have a diameter in the range of 100 nm to 1600 nm, optionally in the range of 200 nm to 1500 nm, and further optionally in the range of 400 nm to 1500 nm. In a non-limiting manner, at least 80% of the primary particles in the oriented secondary particles have a diameter in the range of any two of the following values: 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, etc. Without limitation, the diameter of at least 80% of the primary particles in the oriented secondary particles is within any of the following ranges: 100nm to 500nm, 200nm to 500nm, 400nm to 1600nm, 400nm to 1500nm, 400nm to 1400nm, 400nm to 1350nm, 400nm to 1200nm, 400nm to 1000nm, 450nm to 1600nm, 450nm to 1500nm, 450nm to 1400nm, 450nm to 1350nm, 450nm to 1200nm, 450nm to 1000nm, etc.

[0210] In some embodiments, the diameter of the primary particles in the oriented secondary particles is 100nm to 1600nm, optionally 200nm to 1500nm, and further optionally 400nm to 1500nm. In a non-limiting manner, the diameter of the primary particles in the oriented secondary particles can also be any of the following values ​​or an interval consisting of any two of the following values: 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, etc. Without limitation, the diameter of the primary particles in the oriented secondary particles can also be any of the following ranges: 100nm~500nm, 200nm~500nm, 400nm~1600nm, 400nm~1500nm, 400nm~1400nm, 400nm~1350nm, 400nm~1200nm, 400nm~1000nm, 450nm~1600nm, 450nm~1500nm, 450nm~1400nm, 450nm~1350nm, 450nm~1200nm, 450nm~1000nm, etc.

[0211] In the present application, unless otherwise specified, the “diameter of a primary particle in an oriented secondary particle” refers to the maximum length of the primary particle in each direction.

[0212] In the present application, without limitation, the diameter of the primary particle in the oriented secondary particle can be analyzed based on a cross-sectional view passing through the center of the oriented secondary particle. As mentioned above, the cross section can be obtained using an ion polishing cross-sectional morphology analysis method, and can be statistically analyzed in combination with a microscopic morphology observation method (such as SEM). The diameter of the primary particle can be measured based on the longest axis in the cross section of the primary particle in the cross-sectional view passing through the center of the oriented secondary particle.

[0213] By adjusting the diameter of the primary particles in the oriented secondary particles within the aforementioned range, it is beneficial to control the active crystal surface ratio of the primary particles, so that the lithium ion insertion and extraction kinetics of the primary particles can be further improved.

[0214] In some embodiments, at least 80% of the primary particles in the oriented secondary particles have an L value within the range of 400nm to 1500nm, optionally within the range of 400nm to 1500nm, and further optionally within the range of 400nm to 1400nm. In a non-limiting manner, at least 80% of the primary particles in the oriented secondary particles have an L value within the range of any two of the following values: 400nm, 450nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, etc. Without limitation, at least 80% of the primary particles in the oriented secondary particles have an L value within any of the following ranges: 400nm to 1600nm, 400nm to 1500nm, 400nm to 1400nm, 400nm to 1350nm, 400nm to 1200nm, 400nm to 1000nm, 450nm to 1600nm, 450nm to 1500nm, 450nm to 1400nm, 450nm to 1350nm, 450nm to 1200nm, 450nm to 1000nm, etc.

[0215] In some embodiments, the L value of the primary particles in the oriented secondary particles is in the range of 400nm to 1500nm, optionally in the range of 400nm to 1500nm, and further optionally in the range of 400nm to 1400nm. Non-limitingly, the L value of the primary particles in the oriented secondary particles is in the range of any two of the following values: 400nm, 450nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, etc. Without limitation, the L value of the primary particles in the oriented secondary particles is within any of the following ranges: 400nm to 1600nm, 400nm to 1500nm, 400nm to 1400nm, 400nm to 1350nm, 400nm to 1200nm, 400nm to 1000nm, 450nm to 1600nm, 450nm to 1500nm, 450nm to 1400nm, 450nm to 1350nm, 450nm to 1200nm, 450nm to 1000nm, etc.

[0216] In some embodiments, at least 80% of the primary particles in the oriented secondary particles have a W value in the range of 100nm to 800nm, optionally in the range of 200nm to 700nm, and further optionally in the range of 200nm to 600nm. In a non-limiting manner, at least 80% of the primary particles in the oriented secondary particles have a W value in the range of any two of the following values: 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 650nm, 700nm, 750nm, 800nm, etc. Without limitation, at least 80% of the primary particles in the oriented secondary particles have W values ​​within any of the following ranges: 100nm-700nm, 200nm-800nm, 200nm-600nm, 250nm-800nm, 250nm-700nm, 250nm-600nm, etc.

[0217] In some embodiments, the W value of the primary particles in the oriented secondary particles is in the range of 100nm to 800nm, optionally in the range of 200nm to 700nm, and further optionally in the range of 200nm to 600nm. Without limitation, the W value of the primary particles in the oriented secondary particles is in the range of any two of the following values: 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 650nm, 700nm, 750nm, 800nm, etc. Without limitation, the W value of the primary particles in the oriented secondary particles is in any of the following ranges: 100nm to 700nm, 200nm to 800nm, 200nm to 600nm, 250nm to 800nm, 250nm to 700nm, 250nm to 600nm, etc.

[0218] In some embodiments, the particle size distribution parameter SPAN of the positive electrode active material satisfies 1.1≤SPAN≤1.4, optionally, 1.2≤SPAN≤1.3. Without limitation, the particle size distribution parameter SPAN of the positive electrode active material can also be any of the following values ​​or an interval consisting of any two of the following values: 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, etc.

[0219] By adjusting the particle size distribution parameter SPAN of the positive electrode active material within the aforementioned range, it is beneficial to make the large particles and small particles in the positive electrode active material have appropriate volume proportions, so that the positive electrode active material has a high powder compaction density while having a high capacity, which is beneficial to maximizing the volume energy density of the positive electrode side. By designing the size of the particles, the polycrystalline material formed can increase the volume energy density of the positive electrode material.

[0220] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0221] The D of positive electrode active material v 90Satisfy: 15μm≤D v 90≤18μm, optionally, 16μm≤D v 90≤17μm;

[0222] The D of positive electrode active material v 10: 4μm≤D v 10≤6μm, optionally, 4.5μm≤D v 10≤5.5μm;

[0223] The D of positive electrode active material n10 Satisfied: D n 10≥2μm.

[0224] In some embodiments, D of the positive electrode active material v 90Satisfy: 15μm≤D v 90≤18μm, optionally, 16μm≤D v 90≤17μm. Without limitation, D v 90 can be any of the following values ​​or an interval consisting of any two of the following values: 15μm, 15.5μm, 16μm, 16.5μm, 17μm, 17.5μm, 18μm, etc.

[0225] By controlling the D v 90 Within the aforementioned range, it is beneficial to control the volume ratio of large particles in the material, to control the specific surface area, and to inhibit side reactions.

[0226] In some embodiments, D of the positive electrode active material v 10: 4μm≤D v 10≤6μm, optionally, 4.5μm≤D v 10≤5.5μm. Without limitation, D of the positive electrode active material v 10 can be any one of the following values ​​or a range consisting of any two of the following values: 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, etc.

[0227] By controlling the D v 10 Within the aforementioned range, it is beneficial to control the appropriate volume ratio of small particles in the material and to improve the compaction density of the material.

[0228] In some embodiments, D of the positive electrode active material n 10 Satisfied: D n 10≥2μm

[0229] By controlling the D n 10 Within the aforementioned range, the number of small particles in the material can be controlled within a more appropriate range, which is beneficial for controlling a more appropriate specific surface area, thereby increasing the storage life of the battery.

[0230] In some embodiments, in the oriented secondary particles, the positive electrode active material includes a layered lithium ion active material.

[0231] When the positive electrode active material in the oriented secondary particles includes a layered lithium ion active material, the positive electrode active material including the oriented secondary particles may be obtained by the method exemplified in the present application but is not limited thereto.

[0232] Non-limiting examples of the layered lithium ion active material may include layered lithium transition metal oxides. Non-limitingly, examples of the layered lithium ion active material may include lithium-containing nickel composite oxides, and the like.

[0233] In some embodiments, in the aligned secondary particles, the positive electrode active material includes a lithium-containing nickel composite oxide.

[0234] In the present application, unless otherwise specified, "lithium transition metal oxide" refers to a lithium ion active material containing a transition metal element.

[0235] In this application, unless otherwise specified, "lithium-containing nickel composite oxide" refers to a lithium ion active material containing nickel. It is understood that the lithium-containing nickel composite oxide contains at least lithium, nickel and oxygen, and further, may contain or not contain other types of transition metal elements, such as Zr, Al, Sr, etc. The lithium-containing nickel composite oxide may also contain or not contain non-metallic elements, such as B, C, etc.

[0236] By introducing lithium-nickel composite oxide into the positive electrode active material of the oriented secondary particles, the introduction of nickel element is beneficial to improving the energy density of the positive electrode active material, and is also beneficial to improving the power performance of the battery.

[0237] In this application, unless otherwise specified, the molar ratio of nickel element to oxygen (O) element in the lithium-containing nickel composite oxide is denoted as Q Ni / O .

[0238] In some embodiments, in the oriented secondary particles, 0.3≤Q Ni / O ≤0.5, optionally, 0.4≤Q Ni / O ≤0.5. Without limitation, in the oriented secondary particles, Q Ni / O It can be any of the following values ​​or an interval consisting of any two of the following values: 0.3, 0.35, 0.4, 0.45, 0.5, etc.

[0239] In this application, unless otherwise specified, the molar ratio of nickel element to lithium (Li) element in the lithium-containing nickel composite oxide is denoted as Q Ni / Li .

[0240] In some embodiments, in the oriented secondary particles, 0.6≤Q Ni / Li ≤1, optionally 0.8≤Q Ni / Li ≤1. Without limitation, in the oriented secondary particles, Q Ni / Li It can be any of the following values ​​or an interval consisting of any two of the following values: 0.6, 0.65, 0.66, 2 / 3, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, etc.

[0241] The molar ratio (Q Ni / O ) and / or the molar ratio of nickel to lithium in the lithium-containing nickel composite oxide (Q Ni / Li ) is controlled within the aforementioned range, the positive electrode active material can have a high nickel content, which is more conducive to improving the energy density of the positive electrode active material.

[0242] In some embodiments, the lithium-containing nickel composite oxide comprises at least one of a cobalt (Co) element and an M element, wherein the M element is at least one of an Mn element and an Al element. In some embodiments, the lithium-containing nickel composite oxide comprises a Co element and an Mn element. In some embodiments, the lithium-containing nickel composite oxide comprises a Co element and an Al element.

[0243] In some embodiments, the lithium-containing nickel composite oxide is a lithium-containing nickel-cobalt-manganese composite oxide.

[0244] In this application, unless otherwise specified, "lithium-containing nickel-cobalt-manganese composite oxide" refers to a lithium ion active material containing nickel, cobalt and manganese elements. It is understood that the lithium-containing nickel-cobalt-manganese composite oxide contains at least lithium, nickel, cobalt, manganese and oxygen, and further, may contain or not contain other types of transition metal elements, such as Zr, Al, Sr, etc. The lithium-containing nickel composite oxide may also contain or not contain non-metallic elements, such as B, C, etc.

[0245] In some embodiments, the lithium-containing nickel composite oxide comprises a doping element, Q Ni / O <0.5, the doping element may include but is not limited to at least one of Zr, Al, B, Sr and Ca. In some embodiments, the doping element is selected from one or more of Zr, Al, B, Sr and C. In some embodiments, the doping element is a combination of Zr, Al, B, Sr and C. Ni / O It can be but not limited to 0.3≤Q Ni / O <0.5, optionally 0.4≤Q Ni / O <0.5.

[0246] In some embodiments, at least a portion of the primary particles include a particle body and at least a portion of a coating layer located on the surface of the particle body, the particle body includes a lithium-nickel composite oxide, and the coating layer includes at least one element of Zr, Al, B, Sr and Ca.

[0247] In some embodiments, the primary particle includes a particle body and a coating layer located on at least a portion of the surface of the particle body, the particle body includes a lithium-nickel composite oxide, and the coating layer may include but is not limited to one or more elements of Zr, Al, B, Sr and Ca.

[0248] In some embodiments, the oriented secondary particles satisfy one or more of the following characteristics (any numerical parameter in the following characteristics can also be selected from any suitable numerical value or range in the context):

[0249] In oriented secondary particles, 0.3≤Q Ni / O ≤0.5, optionally, 0.4≤Q Ni / O ≤0.5;

[0250] In oriented secondary particles, 0.6≤Q Ni / Li ≤1, optionally 0.8≤Q Ni / Li ≤1;

[0251] The lithium-containing nickel composite oxide contains at least one of a cobalt element and an M element, wherein the M element is at least one of a Mn element and an Al element;

[0252] The lithium-nickel composite oxide contains a doping element, Q Ni / O <0.5, the doping element includes at least one element among Zr, Al, B, Sr and Ca;

[0253] At least a portion of the primary particles include a particle body and at least a portion of a coating layer located on the surface of the particle body, the particle body includes a lithium-nickel composite oxide, and the coating layer includes at least one element of Zr, Al, B, Sr and Ca.

[0254] By adding Q Ni / O and / or Q Ni / Li When controlled within the aforementioned range, the lithium-nickel composite oxide has a high nickel content and can significantly improve the energy density of the positive electrode active material.

[0255] Introducing cobalt (Co) element into lithium-nickel composite oxide is beneficial to stabilizing the material structure and improving the cycle and rate performance of the positive electrode active material.

[0256] Introducing manganese (Mn) element into lithium-nickel composite oxide is beneficial to reducing cost and improving structural stability of the material.

[0257] Introducing aluminum (Al) elements into lithium-nickel composite oxides can help improve the cycle stability of the material.

[0258] By modifying the lithium-nickel composite oxide by one or more of the above-mentioned doping and the above-mentioned coating, one or more of the following aspects can be achieved: enhancing the stability of the material, improving the energy density of the material, and improving the cycle life. For example, the structure of the lithium-nickel composite oxide can be stabilized by bulk doping. For example, a fast ion conductor coating material can be provided on the surface of the lithium-nickel composite oxide to improve the energy density and cycle life of the material.

[0259] In some embodiments, 0.3≤Q Ni / O ≤0.5, optionally, 0.4≤Q Ni / O ≤0.5, and any suitable range in the context may also be referred to; in the oriented secondary particles, the positive electrode active material includes lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and one or more modified forms of any of the foregoing substances, wherein the modified form includes one or more of doping modification and coating modification, the doping element used for doping modification includes at least one of Zr, Al, B, Sr and Ca, and the coating element used for coating modification includes at least one of Zr, Al, B, Sr and Ca;

[0260] The molar ratio R of nickel and oxygen in the positive electrode active material Ni / O Satisfy 0.4≤R Ni / O ≤0.5.

[0261] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:

[0262] The D of positive electrode active material v 50 is 8μm~11μm, and can be 9μm~10μm;

[0263] The diameter of at least 80% of the primary particles in the oriented secondary particles is 100nm to 1600nm, and can be 400nm to 1500nm;

[0264] The particle size distribution parameter SPAN of the positive electrode active material conforms to the following formula: SPAN = (D v 90-D v 10) / D v 50, wherein 1.1≤SPAN≤1.4, optionally, 1.2≤SPAN≤1.3.

[0265] The positive electrode active material of the oriented secondary particles can be provided with a ternary positive electrode active material with a high nickel content and its modified material. The modified form can include one or more of doping modification and coating modification, which can be used to obtain a ternary positive electrode active material with high energy density and long life. The structure of the ternary positive electrode active material can be stabilized by bulk phase doping, and the energy density and cycle life of the material can be improved by providing a fast ion conductor coating material on the surface of the ternary positive electrode active material. Combined with the regulation of the angle α1 and F1, the orientation and distribution of the primary particles in the secondary particles of the positive electrode active material can be regulated, and the balance between inhibiting the electrolyte from penetrating the interior and optimizing the distance of the lithium ion transmission path can be taken into account, thereby improving the mass energy density of the material and the lithium ion diffusion kinetics. Furthermore, by controlling the D of the positive electrode active material v50. The diameter of the primary particles in the oriented secondary particles and one or more parameters in the particle size distribution parameter SPAN of the positive electrode active material are within the aforementioned range, and the aforementioned related advantages can be further combined. For example, by adjusting the particle size distribution parameter SPAN of the positive electrode active material within the aforementioned range, it is beneficial to make the large particles and small particles in the positive electrode active material have a suitable volume proportion, respectively, which can further improve the powder compaction density of the material and the volume energy density of the positive electrode sheet. By designing the secondary particles to match large and small particles, the polycrystalline material formed can increase the volume energy density of the positive electrode material. Furthermore, the doping and coating modification methods can be combined to improve the bulk structure and surface stability of the material to achieve a longer cycle life.

[0266] In some embodiments, in the oriented secondary particles, the L average value of the inner layer is less than 700nm (optionally, the L average value of the inner layer is less than 660nm), and the L average value of the outer layer is greater than or equal to 720nm (optionally, the L average value of the outer layer is greater than or equal to 750nm).

[0267] Without limitation, in the oriented secondary particles, the L average value of the inner layer can be any of the following values, or less than or equal to any of the following values, or less than any of the following values: 690nm, 680nm, 670nm, 660nm, 650nm, etc.

[0268] Without limitation, in the oriented secondary particles, the L average value of the outer layer can be any of the following values, or greater than or equal to any of the following values, or greater than any of the following values: 720nm, 730nm, 740nm, 750nm, 760nm, 770nm, 780nm, etc.

[0269] In some embodiments, in the oriented secondary particles, the average L value of the inner layer is less than 660 nm, and the average L value of the outer layer is greater than or equal to 750 nm.

[0270] For the positive electrode active material in the oriented secondary particles, including the positive electrode active material containing lithium nickel composite oxide, by controlling the L average value of the inner layer and the outer layer in the oriented secondary particles within the aforementioned range, the outer layer can have a faster active ion deintercalation efficiency, and the inner layer can have a larger angle to better inhibit the electrolyte from penetrating into the grain boundary, which is more conducive to comprehensively improving the actual energy density, cycle performance and kinetic performance of the battery.

[0271] In the present application, unless otherwise specified, a "secondary battery" includes a battery cell.

[0272] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy. Generally, a battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode plate and the negative electrode plate. The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The separator is arranged between the positive electrode plate and the negative electrode plate, which mainly prevents the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0273] In some embodiments, the secondary battery further includes a negative electrode sheet, a separator and an electrolyte, and the separator is located between the positive electrode sheet and the negative electrode sheet.

[0274] In some embodiments, the secondary battery is a lithium ion secondary battery.

[0275] In some embodiments, the secondary battery is a lithium ion secondary battery, and the electrolyte salt may include an electrolyte lithium salt.

[0276] The following are some additional descriptions about the positive electrode.

[0277] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, wherein the positive active material layer includes a positive active material. It can be understood that the positive active material includes the aforementioned oriented secondary particles.

[0278] The positive electrode active material includes a positive electrode active substance.

[0279] The positive electrode active material includes secondary particles, which are aggregated particles including a plurality of primary particles; the primary particles include a positive electrode active material.

[0280] The positive electrode active material in the positive electrode active material can refer to the above description, but is not limited thereto.

[0281] Without limitation, the weight percentage of the positive electrode active material in the positive electrode active material layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.

[0282] In some embodiments, the positive electrode active material layer may also use layered lithium ion active materials that are known in the art and can be used in batteries.

[0283] In some embodiments, the positive electrode active material layer may also use lithium-containing nickel composite oxides that are known in the art and can be used in batteries.

[0284] As a non-limiting example, the layered lithium ion active material may include one or more of the following materials: lithium nickel-containing composite oxides and modified compounds thereof. However, the present application is not limited to these materials. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium nickel-containing composite oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel-containing composite oxides, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and modified compounds thereof. Non-limiting examples of lithium cobalt oxides may include LiCoO 2 Non-limiting examples of lithium-containing nickel composite oxides may include LiNiO 2 Non-limiting examples of lithium manganese oxides may include LiMnO 2 、LiMn 2 O 4 etc.; Non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.80 Co 0.15 Al 0.05 O 2 .

[0285] It is understandable that the battery is accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the Li content in the positive electrode plate is different when the battery is discharged to different states.

[0286] In the exemplary description of the positive electrode active material in this application, unless otherwise specified, the content of Li can be the initial state of the material or the non-initial state after charge and discharge cycles. The positive electrode active material is applied to the positive electrode plate in the battery system. After charge and discharge cycles, the content of Li in the positive electrode active material contained in the positive electrode plate usually changes. Among them, the content of Li can be measured by atomic molar content, but is not limited to this. Taking the wet preparation of positive electrode plates as an example, regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It can be understood that new materials or new substances obtained by appropriate modification on the basis of the listed positive electrode active materials are also within the scope of positive electrode active materials. The aforementioned appropriate modification refers to acceptable modification methods for positive electrode active materials, and non-limiting examples include coating modification.

[0287] In the exemplary description of the positive electrode active material in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the atomic molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by atomic molar content, but is not limited to this.

[0288] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. In the positive electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. In the positive electrode current collector, the composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In a non-limiting manner, in the positive electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0289] In some embodiments, the positive electrode active material layer optionally includes a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Generally, the weight percentage of the binder in the positive electrode active material layer can be 0 to 10wt%, further can be 0 to 8wt%, and further can be 1wt% to 5wt%.

[0290] In some embodiments, the positive electrode active material layer optionally includes a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Typically, the weight percentage of the conductive agent in the positive electrode active material layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 0 to 5 wt%.

[0291] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry. Further, the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. Cold pressing can be performed by a cold rolling mill. The type of solvent in the positive electrode slurry can include but is not limited to any of the aforementioned embodiments, for example, it can include N-methylpyrrolidone (NMP), and further can be NMP. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector, or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt% to 80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s to 25000mPa·s. Based on the single-side coating amount on the positive electrode current collector, when the positive electrode slurry is coated, the coating unit surface density based on dry weight (excluding solvent) can be 13 mg / cm 2 ~20 mg / cm 2 The compaction density of the positive electrode sheet can be 3.0 g / cm 3 ~3.6 g / cm 3 , optional 3.3g / cm 3 ~3.5 g / cm 3 .

[0292] The "compacted density" used in this application has a well-known meaning in the art and is one of the reference indicators of material energy density. In this application, unless otherwise specified, the compacted density of an electrode plate refers to the ratio of the mass of the electrode active material layer to its volume. The compacted density of a positive electrode plate refers to the ratio of the mass of the positive electrode active material layer to its volume, and the compacted density of a negative electrode plate refers to the ratio of the mass of the negative electrode active material layer to its volume.

[0293] The following is some description about the negative electrode.

[0294] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0295] Without limitation, the weight percentage of the negative electrode active material in the negative electrode active material layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.

[0296] As a non-limiting example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on any one or both of the two surfaces facing each other of the negative electrode current collector.

[0297] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as a metal foil, a copper foil may be used. In the negative electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. In the negative electrode current collector, the composite current collector may be formed by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In a non-limiting manner, in the negative electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0298] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials or substances, and other traditional substances that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0299] In some embodiments, the negative electrode active material includes one or more of carbon-based materials, silicon-based materials, tin-based materials, lithium titanate, and modified forms of any of the foregoing materials, wherein the modified forms include one or more of doping modification and coating modification. Both the doping modification method and the coating modification method can adopt or refer to the existing modification methods in the art, including but not limited to the selection of element types and doping amounts. Carbon-based materials may include but are not limited to one or more of graphite materials, soft carbon, hard carbon, etc. Graphite materials may include one or more of artificial graphite and natural graphite.

[0300] In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material. Without limitation, the sum of the mass of the carbon-based material and the silicon-based material in the total mass of the negative electrode active material can be ≥80%, optionally ≥90%, further optionally ≥95%, further optionally ≥96%, etc., further optionally 100%, etc. The sum of the mass of the graphite material and the silicon-based material in the total mass of the negative electrode active material can also be any of the following percentages, or greater than or equal to any of the following percentages and less than or equal to 100%, or selected from the interval consisting of any two of the following percentages: 80%, 82%, 83%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 98%, etc. The definition of carbon-based materials can be found in the above text, for example, the carbon-based material can be a graphite material. The content of the carbon-based material can also refer to any suitable embodiment in the context.

[0301] In some embodiments, the negative electrode active material includes a carbon-based material. Without limitation, the mass percentage of the carbon-based material in the negative electrode active material can be ≥80%, optionally ≥90%, further optionally ≥95%, further optionally ≥96%, etc., further optionally 100%, etc. The mass percentage of the carbon-based material in the negative electrode active material can also be any of the following percentages, or greater than or equal to any of the following percentages and less than or equal to 100%, or selected from the interval consisting of any two of the following percentages: 80%, 82%, 83%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 98%, etc. The definition of carbon-based materials can be found in the above text, for example, the carbon-based material can be a graphite material.

[0302] In some embodiments, the negative electrode active material layer may optionally include a binder. In a non-limiting manner, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). In a non-limiting manner, the weight percentage of the binder in the negative electrode active material layer may be 0wt% to 20wt%, further 0wt% to 10wt%, further 0 to 5wt%, further 1wt% to 5wt%, and further optionally 1wt% to 3wt%.

[0303] In some embodiments, the negative electrode active material layer may optionally include a conductive agent. Without limitation, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Without limitation, the weight percentage of the conductive agent in the negative electrode active material layer may be 0wt% to 15wt%, further optionally 0wt% to 10wt%, and further optionally 0wt% to 5wt%.

[0304] In some embodiments, the negative electrode active material layer may optionally include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)), etc. In a non-limiting manner, the weight percentage of other additives in the negative electrode active material layer may be 0wt% to 15wt%, further optionally 0wt% to 10wt%, further optionally 0wt% to 5wt%, further optionally 0wt% to 3wt%.

[0305] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry. Further, the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. Cold pressing can be performed using a cold rolling mill. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 30wt% to 70wt%, and can be optionally 40wt% to 60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s to 10000mPa·s, and can be optionally 3000mPa·s to 10000mPa·s. Based on the single-side coating amount on the negative electrode current collector, when the negative electrode slurry is coated, the coating unit surface density based on dry weight (excluding solvent) can be 6.5 mg / cm 2 ~13mg / cm 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~2.0g / cm 3 , optional 1.0g / cm 3 ~1.8g / cm 3 .

[0306] The electrolyte is exemplarily described below.

[0307] The electrolyte has the function of conducting ions between the positive electrode plate and the negative electrode plate. Unless otherwise specified, the electrolyte includes a liquid electrolyte.

[0308] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0309] In some embodiments, the electrolyte is a non-aqueous electrolyte. The non-aqueous electrolyte may include an electrolyte salt and a solvent.

[0310] The concentration of the electrolyte salt in the electrolyte solution may generally be 0.5 mol / L to 5 mol / L, such as 0.5 mol / L, 1 mol / L, 1.5 mol / L, etc., but is not limited thereto.

[0311] In some embodiments, the electrolyte salt includes an electrolyte lithium salt. Without limitation, the electrolyte lithium salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0312] In some embodiments, the secondary battery is a lithium ion secondary battery, and the electrolyte salt may include an electrolyte lithium salt.

[0313] In some embodiments, the solvent in the non-aqueous electrolyte may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0314] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0315] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0316] In some embodiments, the electrolyte includes a solvent including at least one cyclic carbonate and at least two linear carbonates.

[0317] In some embodiments, in the electrolyte, the solvent includes C 3-6 Cyclic carbonate, C 4-10 The first chain carbonate and C 3-8 The second chain carbonate, wherein the number of carbon atoms of the first chain carbonate is greater than the number of carbon atoms of the second chain carbonate.

[0318] In some embodiments, in the electrolyte, C 3-6 Cyclic carbonates include ethylene carbonate, C 4-10 The first chain carbonate includes diethyl carbonate, C 3-8 The second chain carbonate includes dimethyl carbonate.

[0319] The separator is exemplarily described below.

[0320] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0321] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0322] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and may be 12 μm to 20 μm.

[0323] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0324] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0325] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0326] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.

[0327] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.

[0328] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.

[0329] In some embodiments, the electrolyte injection coefficient is greater than or equal to 1.6 g / Ah.

[0330] The secondary battery may be a battery module 4 or a battery pack 1 .

[0331] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.

[0332] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0333] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0334] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0335] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0336] In a second aspect of the present application, a positive electrode active material is provided, which includes the aforementioned oriented secondary particles.

[0337] In some embodiments, the positive electrode active material includes secondary particles, which are agglomerated particles including primary particles; the primary particles include the positive electrode active material;

[0338] In any secondary particle, the direction from the center of the secondary particle to the surface is recorded as the X direction; the X direction passing through the center of any primary particle is recorded as the longitudinal direction; in any primary particle, the longest axis of the primary particle is recorded as the a-axis;

[0339] The secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, where 15°≤α1≤45°, and F1≥60%.

[0340] The positive electrode sheet prepared using the above-mentioned positive electrode active material can be used to prepare a secondary battery with high energy density, good kinetic performance and long cycle life. By using the orientation angle and quantity ratio of the primary particles included in the oriented secondary particles in the positive electrode active material, it is possible to inhibit the electrolyte from penetrating into the grain boundary of the secondary particles, which is beneficial to inhibit the side reaction between the electrolyte and the surface of the positive electrode active material, and can improve the actual gram capacity and cycle life of the positive electrode active material. It can also achieve a shorter active ion deintercalation path, which is beneficial to promote the rapid deintercalation of active ions during the charge and discharge process, which can improve the actual energy density of the secondary battery and make the secondary battery have good kinetic performance.

[0341] In some embodiments, a positive electrode active material in a secondary battery described in the first aspect of the present application is provided.

[0342] In yet another aspect of the present application, a method for preparing a positive electrode active material is provided, which can be used to prepare the aforementioned positive electrode active material.

[0343] In some embodiments, a method for preparing a positive electrode active material is provided, comprising the following steps:

[0344] S10: preparing a precursor; and

[0345] S20: sintering a first mixture including a precursor and a lithium source for the first time at a temperature T1 to obtain a first sintered product, and then sintering a second mixture including the first sintered product for a second time at a temperature T2 to obtain a positive electrode active material; wherein T1>T2.

[0346] In step S10 , the type of transition metal element in the precursor may be selected according to the crystal structure required by the positive electrode active material, and then a suitable metal source may be selected.

[0347] Step S10 may use a co-precipitation method to prepare the precursor, but is not limited to this.

[0348] In the above-mentioned embodiment, the temperature T1 is higher than the temperature T2. Therefore, the temperature conditions for the first sintering can be described as "high temperature conditions" and the temperature conditions for the second sintering can be described as "low temperature conditions".

[0349] In some embodiments, the temperature T1 for the first sintering may be 700°C to 800°C, such as 700°C, 720°C, 740°C, 750°C, 760°C, 780°C, 800°C, etc., and may also be selected from the range consisting of any two of the above temperatures. Further, the sintering time for the first sintering may be 15h to 30h, such as 15h, 16h, 18h, 20h, 22h, 24h, 25h, 26h, 28h, 30h, etc., and may also be selected from the range consisting of any two of the above time lengths.

[0350] In some embodiments, the temperature T2 for the second sintering may be 200°C to 500°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, etc., and may also be selected from the range consisting of any two of the aforementioned temperatures. Further, the sintering time for the second sintering may be 3h to 8h, such as 3h, 4h, 5h, 6h, 7h, 8h, etc., and may also be selected from the range consisting of any two of the aforementioned time lengths.

[0351] After step S10, a laser particle size analyzer may be used to perform testing to obtain the particle size and SPAN value of the precursor particles, thereby screening precursors with a suitable particle size range and SPAN value for step S20.

[0352] If not otherwise specified, at least one of the first sintering and the second sintering is performed in an oxygen-containing atmosphere. In some embodiments, both the first sintering and the second sintering are performed in an oxygen atmosphere.

[0353] In step S20, the molar ratio of the precursor to the lithium source can be 1:(1.03-1.07) based on OH, such as 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, etc., but not limited thereto. Considering the lithium loss during the sintering process, lithium is usually slightly excessive.

[0354] In step S20, when the first sintering is performed, the first mixture may further include a dopant for introducing a doping element. It is understood that, under normal doping amounts, the introduction of the doping element generally does not affect the crystal structure type of the grains.

[0355] In step S20, when the second sintering is performed, the second mixture may further include a coating agent for introducing a coating element. It is understood that the introduction of the coating element may form a coating layer on at least a portion of the surface of the particles obtained from the first sintering product.

[0356] Without limitation, based on the precursor, doping modification and coating modification can be performed simultaneously.

[0357] Taking the positive electrode active material including a lithium-nickel composite oxide as an example, in some embodiments, a method for preparing a positive electrode active material is provided, including steps S10 and S20, wherein step S10 is S100, and step S20 is S200.

[0358] S100: preparing a nickel-containing precursor.

[0359] The nickel-containing precursor can be prepared by a method including the following steps: according to the element composition in the target chemical formula of the positive electrode active material, the metal source including the nickel source is dissolved in water according to the required type and amount to prepare a metal solution; the metal solution, the complexing agent and the precipitant are mixed, a coprecipitation reaction is carried out under dispersion conditions, solid-liquid separation, washing, and drying to obtain the nickel-containing precursor. The nickel-containing precursor is the corresponding metal hydroxide.

[0360] In step S100, by controlling the type of metal source, the grain structure and particle morphology in the positive electrode active material can be regulated by controlling the type of transition metal element in the nickel-containing precursor. For example, using a metal source including a nickel source can be used to prepare a layered lithium ion active material containing nickel.

[0361] In some embodiments, the lithium-containing nickel composite oxide is a lithium-containing nickel-cobalt-manganese composite oxide. In this case, the metal source may include a nickel source, a cobalt source, and a manganese source. The appropriate amount ratio of the nickel source, the cobalt source, and the manganese source may be selected according to the Ni:Co:Mn molar ratio in the target chemical formula.

[0362] Typically, a metal source is used to provide the transition metal in the nickel-containing precursor.

[0363] The metal source may be a soluble salt of the corresponding metal. For example, a lithium-nickel composite oxide may be provided by a soluble nickel salt (e.g., nickel sulfate); for example, a lithium-nickel-cobalt-manganese composite oxide may be provided by a soluble cobalt salt (e.g., cobalt sulfate) and a soluble manganese salt (e.g., manganese sulfate) to provide a cobalt source and a manganese source, respectively. 0.82 Co 0.12 Mn 0.06 O 2 Taking the nickel-containing precursor as an example, nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 82:12:6 can be used as metal sources.

[0364] A non-limiting example of the complexing agent may include aqueous ammonia.

[0365] In some embodiments, the molar ratio of ammonia to metal element is 1 to 2, non-limiting examples include 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc., and can also be selected from the range of any two of the above values. Ammonia can be made excessive to provide sufficient complexation. By adjusting the amount of ammonia water, the orientation of the primary particles in the secondary particles and the morphology of the secondary particles can be affected.

[0366] In some embodiments, in the coprecipitation reaction system, the concentration of ammonia is 0.3 mol / L to 1 mol / L, with non-limiting examples such as 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc., and can also be selected from the range consisting of any two of the foregoing concentrations.

[0367] In some embodiments, the precipitant is an alkaline agent. Non-limiting examples of precipitants can include alkali metal hydroxides. Non-limiting examples of alkali metal hydroxides can include sodium hydroxide.

[0368] In some embodiments, the reaction temperature for the coprecipitation reaction can be 40°C to 60°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, etc., and can also be selected from the range consisting of any two of the aforementioned temperatures.

[0369] In some embodiments, the pH of the reaction system for the coprecipitation reaction can be 11.2 to 11.8, for example, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, etc., and can also be selected from the range consisting of any two of the aforementioned pH values. By adjusting the pH of the reaction system, the orientation of the primary particles in the secondary particles and the morphology of the secondary particles can be affected.

[0370] In some embodiments, the reaction temperature for the coprecipitation reaction may be 40° C. to 60° C., and the pH may be 11.2 to 11.8. The selection of temperature conditions may affect the growth process of the primary particles, and may also affect the orientation behavior of the primary particles during the growth process.

[0371] In a non-limiting manner, the dispersion condition may be a stirring method. In some embodiments, the stirring rate is 400 rpm to 1000 rpm, and may also be 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc., and may also be selected from the range consisting of any two of the aforementioned stirring rates. By adjusting the stirring rate, the orientation of the primary particles in the secondary particles and the morphology of the secondary particles may also be affected.

[0372] After step S100, a laser particle size analyzer may be used to perform testing to obtain the particle size and SPAN value of the nickel-containing precursor particles, thereby selecting a nickel-containing precursor with a suitable particle size range and SPAN value for step S200.

[0373] S200: performing a first sintering and a second sintering to obtain a positive electrode active material including a lithium-containing nickel composite oxide.

[0374] In some embodiments, S200 includes the following steps: in an oxygen-containing atmosphere, sintering a first mixture including a nickel-containing precursor and a lithium source for a first time at a temperature T1 to obtain a first sintered product, and then sintering a second mixture including the first sintered product for a second time at a temperature T2 to obtain a positive electrode active material including a lithium-nickel composite oxide; wherein T1 is higher than T2.

[0375] In some embodiments, the lithium source is lithium hydroxide.

[0376] In some embodiments, the molar ratio of the nickel-containing precursor to the lithium source can be 1:(1.03-1.07), such as 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, etc., based on OH, but not limited thereto. Considering the lithium loss during the sintering process, lithium is usually slightly excessive.

[0377] In some embodiments, the steps of performing the first sintering and the second sintering include: first performing the first sintering at a temperature T1 to obtain a first sintered product, and then performing the second sintering at a temperature T2; T1>T2. In this case, the first sintering can be called high-temperature sintering, and the second sintering can be called low-temperature sintering.

[0378] In some embodiments, after the first sintering is completed, the first sintered product is obtained by crushing, washing and drying.

[0379] In some embodiments, (T2-T1) ≥ 200°C, optionally, 200°C ≤ (T2-T1) ≤ 600°C, further optionally, 200°C ≤ (T2-T1) ≤ 400°C. Without limitation, (T2-T1) may also be any of the following values ​​or an interval consisting of any two of the following values: 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, etc.

[0380] In some embodiments, the sintering time t1 for the first sintering is greater than the sintering time t2 for the second sintering, t1>t2.

[0381] In some embodiments, T1 may be 700°C to 800°C, such as 700°C, 720°C, 740°C, 750°C, 760°C, 780°C, 800°C, etc., and may also be selected from the range consisting of any two of the above temperatures. Further, the sintering time for the first sintering may be 15h to 30h, such as 15h, 16h, 18h, 20h, 22h, 24h, 25h, 26h, 28h, 30h, etc., and may also be selected from the range consisting of any two of the above time lengths.

[0382] In some embodiments, T2 may be 200°C to 500°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, etc., and may also be selected from the range consisting of any two of the above temperatures. Further, the sintering time for the second sintering may be 3h to 8h, such as 3h, 4h, 5h, 6h, 7h, 8h, etc., and may also be selected from the range consisting of any two of the above time lengths.

[0383] In a non-limiting manner, a dopant may be introduced during the first sintering, and the first mixture including the nickel-containing precursor, the lithium source and the dopant may be sintered for the first time to achieve doping modification and introduce a doping element into the positive electrode active material. The dopant may not be introduced. The types of doping elements may refer to the examples in the context.

[0384] In a non-limiting manner, a coating agent may be introduced during the second sintering, and the second mixture including the first sintered product and the coating agent may be subjected to a second sintering to achieve coating modification and form a positive electrode active material with a coating layer, wherein the coating layer includes a coating element provided by the coating agent. The coating agent may not be introduced. The type of coating element may refer to the examples in the context.

[0385] Without limitation, based on the nickel-containing precursor, doping modification and coating modification can be performed simultaneously.

[0386] The element structure and element composition of the precursor and the positive electrode active material can be determined by the structural and elemental composition analysis methods of the positive electrode active material known in the art. For example, the structure of the particles can be analyzed by ion polishing cross-sectional morphology analysis combined with scanning electron microscopy (SEM) and other methods, such as analyzing the presence or absence of a coating layer. As a non-limiting example, an IB-19500CP ion cross-sectional polisher can be used to polish the pole piece sample to obtain a polished sample with a cut surface; further, the ZEISS sigma 300 device can be used to test the sample. For another example, an inductively coupled plasma spectrometer (ICP instrument, such as iCAP 7400 and other models) can be used to analyze the types and proportions of elements to determine the chemical formula of the precursor and the positive electrode active material.

[0387] The particle size and distribution of the positive electrode active material and the size and orientation of the primary particles in the secondary particles are affected by the precursor preparation process and the sintering process. The above only describes some of the influence relationships. For example, the choice of sintering temperature can also affect the stacking mode of the primary particles, and then affect the orientation distribution of the primary particles.

[0388] The positive electrode active material including the oriented secondary particles can be obtained by the above method. Taking the preparation of the positive electrode active material including the lithium nickel composite oxide as an example, by adjusting the selection of transition metal elements in the metal source, the coprecipitation reaction temperature, the coprecipitation reaction pH value, the amount of the complexing agent (such as ammonia water), the amount of the precipitating agent (such as sodium hydroxide), the dispersion speed (dispersion method such as stirring), the particle size and distribution of the precursor (such as the D v50, SPAN value), sintering method (such as temperature gradient design method), sintering temperature and sintering time and other parameters, one or more of which can adjust the growth, stacking and orientation behavior of the primary particles, thereby affecting the size and morphology of the secondary particles formed and the size, orientation and orientation distribution of the primary particles in the secondary particles. The angle α1 (the angle formed by the a-axis of the primary particle and the longitudinal direction) and F1 (the proportion of the number of primary particles with the a-axis and the longitudinal direction forming an angle α1 in the oriented secondary particles) can be adjusted within the aforementioned range. Please refer to the embodiments below. In addition, the way in which the angle α1 deviates from the corresponding longitudinal direction (for example, it can be a clockwise deviation or a counterclockwise deviation), the anisotropy index I of the angle α1 can also be adjusted by adjusting one or more of the aforementioned parameters. α1 The R of the primary particles can also be adjusted by adjusting one or more of the above parameters. L / W and its distribution parameters (such as the inner R L / W Average value (R MI ), the outer layer R L / W Average value (R MO )) and other characteristic parameters). R can be achieved by adjusting the pH value and adding seed crystals. MI <R MO , including R that can achieve primary particles L / W The value increases from the center of the oriented secondary particle to the surface of the oriented secondary particle.

[0389] In yet another aspect of the present application, a positive electrode plate is provided, which includes a positive electrode active material layer, and the positive electrode active material layer includes the positive electrode active material described in the second aspect of the present application.

[0390] In a third aspect of the present application, an electrical device is provided, which includes the secondary battery described in the first aspect of the present application and at least one of the positive electrode active materials described in the second aspect of the present application.

[0391] In some embodiments, the present application also provides an electrical device, which includes a secondary battery of any embodiment provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, electric motorcycles, electric tools, etc., but are not limited thereto. The electrical device can also be used in the fields of military equipment, aerospace, etc., and can also be used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations.

[0392] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0393] Figure 8 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0394] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0395] Below, some embodiments of the present application are described. The described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be understood as limitations on the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0396] If the techniques or conditions are not specified in the examples, the above description, or the techniques or conditions described in the literature in the field, or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially, or can be synthesized in a conventional manner from commercially available products.

[0397] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0398] In the following examples, room temperature refers to 20°C to 30°C.

[0399] The instruments involved in the following test and analysis methods are non-limiting examples, and those skilled in the art may also use other types of equipment or similar methods to perform test and analysis.

[0400] Test analysis method

[0401] 1. Structural and elemental analysis

[0402] The chemical formula was determined by analysis using an inductively coupled plasma spectrometer (ICP).

[0403] Test instrument: iCAP 7400.

[0404] 2. D v 50. D v 90.D v10 and D n 10Testing and SPAN analysis.

[0405] Testing instrument: Laser particle size analyzer Mastersizer 3000.

[0406] Method: Take a clean beaker, weigh an appropriate amount of the sample to be tested, add 20ml of ethanol to disperse (the sample concentration maintains a light shielding degree of 25%-30%), and fully disperse the sample with ultrasound at 250W / 3min. Pour the sample into the injection tower and circulate it with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light. Refer to GB / T19077-2016 / ISO 13320:2009 standard.

[0407] Draw a particle size volume distribution diagram based on the test data, and get D from the particle size volume distribution diagram v 50. D v 90.D v 10. SPAN=(D v 90-D v 10) / D v 50. Draw a particle size distribution diagram based on the test data, and get D from the particle size distribution diagram n 10.

[0408] Some test results can be found in Table 3.

[0409] 3. Structural observation and statistical analysis of primary particles in secondary particles.

[0410] A focused ion beam electron microscope or an ion cross-section polisher is used to cut the secondary particles in the positive electrode active material layer of the positive electrode plate to obtain a cross-sectional view that basically passes through the center of the secondary particles, and the primary particle information in the cross-sectional view is further analyzed in combination with a scanning electron microscope (SEM) test image.

[0411] (1) Focused ion beam electron microscope (FEI Scios 2HiVac equipment) or ion cross-section polisher.

[0412] The secondary particles were cut to expose a cross section substantially passing through the center of the secondary particles, and SEM observation was performed.

[0413] (2) Scanning electron microscopy (SEM)

[0414] Equipment: Apreo 2SEM field emission scanning electron microscope or ZEISS Sigma 300 scanning electron microscope.

[0415] Sample preparation method: Cut a sample of appropriate size (such as 5mm×5mm) and stick it on a sample table with conductive glue.

[0416] The test parameters for Apreo 2SEM are: accelerating voltage (HV) 2.00kV, detector T1, OptiPlan mode, and probe current 50pA. The working distance, magnification, and horizontal field width can be selected according to the particle size. Figure 2 The cross-sectional view of the oriented secondary particles shown. Figure 2 In the test, the working distance (WD) is about 4.16mm, the magnification (Mag) is 6500X, and the horizontal field of view width (HFW) is 19.5μm.

[0417] (3) Analysis of primary particle information in secondary particles.

[0418] refer to Figure 1 The schematic diagram is used to measure the parameters such as α1 of the primary particles, the direction in which α1 deviates from the radial direction of the secondary particles, L, W, etc., and the F1, R L / W , R MI , R MO ,I α1 Some analysis results can be found in Tables 2 and 3.

[0419] From the SEM test results of the cross-section through the center of the secondary particle, the cross-section showing the outer peripheral outline of the complete secondary particle cross section is selected for the information statistics of the primary particle.

[0420] Select a certain number of primary particles N0 (N0 ≥ 12), outline the outer contour of the primary particle section in the cross-sectional diagram in an elliptical manner, and measure the maximum length value as the test value of the "diameter of the primary particle". The direction of the maximum length is recorded as the a-axis direction, and the straight line line1 passing through the center of the secondary particle and the center of the primary particle is determined. The measured value of the angle between the a-axis and the straight line line1 is recorded as α1; the distance between the two intersection points of the straight line line1 and the outer contour of the primary particle is recorded as L; determine the straight line line2 perpendicular to line1, and the distance between the two intersection points of the straight line line2 and the outer contour of the primary particle is recorded as W. Then R L / W =L / W. Figure 1 .

[0421] Taking the distance R from the center of the secondary particle to the surface of the secondary particle as the reference, the area from the center of the secondary particle (i.e., 0R) to 2 / 3R is recorded as the "inner layer", and the area from 2 / 3R to the outer contour of the secondary particle (i.e., 1R) is recorded as the "outer layer". Based on the cross-sectional profile of the oriented secondary particle, the intersection between the longest axis and the shortest axis in the cross-section of the oriented secondary particle is taken as the center of the oriented secondary particle.

[0422] The center of the primary particle is counted. When the center of the primary particle falls into the inner layer area, it is counted in the inner layer; when the center of the primary particle falls into the outer layer area, it is counted in the outer layer; when the center of the primary particle is at the boundary between the inner layer and the outer layer, it is counted in the "inner layer."

[0423] According to the R L / W Statistics of the inner layer can be used to calculate the R L / W Average value (R MI ) and the outer R L / W Average value (R MO ).

[0424] The number of angles of 15°≤α1≤45° is counted and recorded as N1, then F1=N1 / N0×100%. F1 is the percentage of primary particles whose a-axis forms an angle of 15°≤α1≤45° with the corresponding longitudinal direction in the oriented secondary particles.

[0425] α1 deviates from the radial direction of the secondary particles: When α1 deviates from the straight line L in the clockwise direction, it is marked as "+" and the counting result is N. 1 ; When α1 deviates from the straight line L in the counterclockwise direction, it is marked as “-” and the counting result is N 2 ; When α1 is not within the range of 15°≤α1≤45°, it is marked as “other”. α1 =N1 / N2.

[0426] (4) The percentage of oriented secondary particles in the secondary particles.

[0427] According to the cross-sectional view of at least 10 randomly selected secondary particles, according to the SEM analysis results of the cross-sectional view through the center of the secondary particle, it is judged whether it is an oriented secondary particle. When 15°≤α1≤45°, F1≥60%, it is counted as one oriented secondary particle; if α1 is not within the above range or F1<60%, the oriented secondary particle is not counted. According to the counting results, the percentage of the number of oriented secondary particles is calculated, and this value is used as the test value of "the percentage of the number of oriented secondary particles in the secondary particles P2".

[0428] Some of the results can be found in Table 3.

[0429] 4. Characterization of positive electrode active materials

[0430] (1) Powder compaction density

[0431] The powder compaction density can be determined by conventional methods in the art.

[0432] Testing instrument: electronic pressure testing machine or compaction density meter.

[0433] Test method using electronic pressure testing machine as an example: Take a certain mass m 0 The powder is placed in the mold of the electronic pressure testing machine, and the bottom area of ​​the mold is recorded as A 0 , adjust the pressure to 4T, maintain the pressure for 30s, and read the height h of the powder block 0 According to the formula ρ=m 0 / (A 0 ×h 0 ), calculate the powder compaction density ρ at 4T.

[0434] The test method using the compaction density meter as an example: Take a certain mass m 0 The powder is placed in a special compaction mold, and the bottom area of ​​the mold is recorded as A 0 Then put the mold on the compaction density meter, apply a pressure of 4T, maintain the pressure for 30s, and record the thickness of the powder block after unloading. 0 According to the formula ρ=m 0 / (A 0 ×h 0 ), calculate the powder compaction density ρ at 4T.

[0435] Some of the results can be found in Table 3.

[0436] (2) Lithium ion solid phase diffusion coefficient test:

[0437] Taking the GITT method as an example, the steps for testing the lithium ion solid phase diffusion coefficient of the positive electrode active material are as follows:

[0438] The test temperature is 25°C, and the positive electrode active material is ground into a powder microelectrode; the powder microelectrode is connected to the electrochemical workstation for coulometric titration. The GITT curve is obtained with a pulse current of 20μA, a titration time of 1h, and an interval of 4h (Note: to compare the effects of pulse current and time, a parallel experiment of 10μA and 10min can be performed). The lithium ion diffusion coefficient D is calculated using the following formula:

[0439]

[0440] Where D is the lithium ion diffusion coefficient; I 0 The pulse current applied is 20μA; V mis the molar volume of the positive electrode active material; F is the Faraday constant; A is the electrode surface area, n is the charge number of the lithium ion, n is 1; dE / dx is the slope of the coulomb titration curve, that is, the slope of the open circuit potential at a certain concentration on the Li concentration curve in the electrode; dE / d(t1 / 2) is the slope of the polarization voltage versus t1 / 2 curve. For more details, please refer to the literature: Xie et al., Solid State Ionics, 2007, 178: 1218–1224; Yang et al., Electrochimica Acta, 2012, 66: 88–93.

[0441] Some of the results can be found in Table 3.

[0442] 5. Battery performance test

[0443] (1) Volumetric energy density

[0444] The cell volume of the secondary battery is recorded as V 0 .

[0445] Capacity test: Charge at 1 / 3C constant current to 3.65V, then charge at 3.65V constant voltage to current 0.05C, leave for 5 minutes, then discharge at 1 / 3C to 2.5V, and obtain capacity C 0 , the voltage platform is denoted as U.

[0446] Then the volume energy density of the battery VED = C 0 ×U / V 0 .

[0447] Some of the results can be found in Table 3.

[0448] (2) Cyclic performance test

[0449] At 25°C, the battery to be tested is charged at a constant current of 1C to a voltage of 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C, left for 5 minutes, and then discharged at a constant current of 1C to a voltage of 2.8V. The resulting capacity is recorded as the initial capacity C. 0 Repeat the above steps for the same battery and record the discharge capacity C of the battery after the nth cycle. n , then the battery capacity retention rate P after the nth cycle n =C n / C 0 × 100%. The cycle is continued until the cell capacity retention rate decays to 80%.

[0450] The battery capacity retention rate recorded at 900 cycles can be found in Table 3.

[0451] Example 1.

[0452] 1. Preparation of positive electrode active materials

[0453] Preparation of nickel-containing precursor: According to the target chemical formula (LiNi 0.82 Co 0.12 Mn 0.06 O 2 ), nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate are dissolved in deionized water to prepare a metal solution with a molar ratio of Ni:Co:Mn of 82:12:6, and the metal solution, complexing agent ammonia water and precipitant sodium hydroxide solution are pumped into the reactor for coprecipitation reaction. The entire reaction process is protected by inert gas (nitrogen), the temperature of the reaction system is 40°C to 60°C, the pH is between 11.2 and 11.8, the molar ratio of ammonia to metal elements is between 1 and 2, and the stirring rate is 400rpm to 1000rpm. After the reaction is completed, a precursor is obtained through washing, drying and other processes, which is a metal hydroxide.

[0454] Sintering the nickel-containing precursor to prepare the lithium-containing nickel composite oxide positive electrode active material: the prepared nickel-containing precursor and the lithium source lithium hydroxide are mixed evenly, and oxygen (O 2 ) is subjected to the first sintering, the high temperature sintering temperature is 700℃~800℃(T1), the sintering time is 15h~30h(t1), and the prepared material is subjected to the processes of crushing, washing, drying, etc. to obtain the first sintering product; the first sintering product is subjected to the second low temperature sintering, the low temperature sintering temperature is 200℃~500℃(T2), the sintering time is 3h~8h(t2), and the ternary positive electrode active material is obtained.

[0455] In this example, the reaction temperature of the co-precipitation method is 50°C, the pH is controlled at 11.5±0.2, the molar ratio of ammonia to metal elements is 1.2, the stirring speed is 600rpm, the nickel-containing precursor and the lithium source lithium hydroxide are mixed in a molar ratio of 1:1.05 (in terms of OH), the high-temperature sintering temperature (T1) is 780°C, the high-temperature sintering time (t1) is 20h, the low-temperature sintering temperature (T2) is 400°C, and the high-temperature sintering time (t2) is 4h.

[0456] 2. Preparation of secondary batteries

[0457] (1) Preparation of positive electrode sheet

[0458] The positive electrode active material, conductive carbon black and polyvinylidene fluoride (PVDF) prepared above were mixed in a mass ratio of 97.44:1.56:1 and added to the solvent N-methylpyrrolidone to obtain positive electrode slurry. The positive electrode slurry was coated on both surfaces of the aluminum foil and dried in a vacuum oven at 100°C to 120°C for 8h to 10h. After cold pressing and cutting, the positive electrode sheet was obtained. The coating surface density on one side is 0.25g / (1540.25mm 2), about 16.23 mg / cm 2 .

[0459] (2) Preparation of negative electrode sheet

[0460] Graphite, styrene butadiene rubber, conductive carbon and sodium carboxymethyl cellulose were added to deionized water in a mass ratio of 96.5:1.8:0.7:1, and mixed evenly to obtain negative electrode slurry. The negative electrode slurry was coated on both surfaces of the copper foil, dried in a drying oven, cold pressed and cut to obtain negative electrode sheets. The coating surface density on one side is 0.16g / (1540.25mm 2 ), about 10.39 mg / cm 2 .

[0461] (3) Isolation film

[0462] Choose conventional polypropylene film (PP film).

[0463] (4) Electrolyte

[0464] Ethylene carbonate, diethyl carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1:1, and LiPF 6 Dissolved in the above-mentioned mixed solvent to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L.

[0465] (5) Assembling secondary batteries

[0466] Placed in the order of "separator-negative electrode sheet-separator-positive electrode sheet", one end of the positive electrode sheet, negative electrode sheet and two separators are fixed to the discharge roller, and the other end is stacked together and fixed to the winding shaft. The winding shaft is rotated by a motor to wind up the positive electrode sheet, negative electrode sheet and two separators to obtain a wound battery cell (wound electrode assembly).

[0467] The electrode assembly is placed in an aluminum shell, baked at 80°C to remove water, then the electrolyte is injected and sealed. After going through the processes of standing, hot and cold pressing, formation, shaping, and capacity testing, a secondary battery is obtained.

[0468] Example 2-5. A positive electrode active material and a secondary battery are prepared by a method substantially the same as that of Example 1. The difference is that the steps for preparing the positive electrode active material are adjusted, and one or more of the following parameters are mainly adjusted: the pH of the coprecipitation reaction system in the precursor preparation step, the concentration of the complexing agent ammonia water (to control the pH in the range of 11.2 to 11.8, the amount of sodium hydroxide can be adjusted accordingly), the reaction temperature and reaction time of the coprecipitation reaction and the stirring rate, the sintering temperature T1 and sintering time t1, sintering temperature T2 and sintering time t2 in the precursor sintering step. The main adjustment parameters can be referred to Table 1, and the parameters not involved in Table 1 can be appropriately adjusted according to the above description.

[0469] Example 6. A positive electrode active material and a secondary battery are prepared by a method substantially the same as that of Example 1. The difference is that in the step of preparing the positive electrode active material, a nickel-containing precursor is prepared according to LiNi 0.6 Co 0.2 Mn 0.2 O 2 The molar ratio of the nickel source, the cobalt source and the manganese source was adjusted to 6:2:2.

[0470] Comparative Example 1.

[0471] The positive electrode active material and the secondary battery were prepared by the method substantially the same as that in Example 1. The difference was that the steps for preparing the positive electrode active material were different, wherein in the step of preparing the precursor, the pH was 11.0±0.2, the molar ratio of ammonia to the metal element was 1.0, the stirring rate was 500 rpm, and the sintering temperature T1 in the step of sintering the precursor was 750°C.

[0472] This comparative example obtains a positive electrode active material with a relatively low F1; F1 is the percentage of primary particles whose a-axis forms an angle of 15°≤α1≤45° with the corresponding longitudinal direction in the oriented secondary particles.

[0473] Comparative Example 2.

[0474] The positive electrode active material and the secondary battery were prepared by the method basically the same as that in Example 1. The difference is that the steps for preparing the positive electrode active material are different, wherein in the step of preparing the precursor, the coprecipitation reaction temperature is 55°C, the pH is 11.2±0.2, the molar ratio of ammonia to the metal element is 1.1, and the stirring rate is 450 rpm; the second sintering is performed first, and then the first sintering is performed.

[0475] Preparation of lithium-nickel composite oxide positive electrode active material: The nickel-containing precursor is sintered at 450° C. for 8 hours, and after crushing, washing, drying and other processes, it is evenly mixed with lithium source lithium hydroxide and sintered at 720° C. for 18 hours.

[0476] This comparative example obtains a positive electrode active material in which most of the primary particles in the secondary particles have a smaller α1. According to statistical results, the α1 is less than 10°, that is, it can be considered that there are basically no oriented secondary particles.

[0477] The parameters for preparing the positive electrode active materials of Examples 2-6 and Comparative Examples 1-2 can also be found in Table 1.

[0478] Table 1.

[0479]

[0480] Test analysis results:

[0481] In Example 1-6, positive electrode active materials were prepared using lithium-containing nickel oxide as an example. According to the elemental analysis results, the elemental composition of the positive electrode active material was substantially consistent with the target chemical formula.

[0482] The positive electrode active materials prepared in the above Examples 1-6 all meet the following characteristics:

[0483] (1) There are oriented secondary particles with 15°≤α1≤45° and F1≥60%. In some embodiments, the oriented secondary particles satisfy F1≥70%, and in some embodiments, F1 exceeds 80%;

[0484] (2) The proportion of the number of oriented secondary particles in the secondary particles of the positive electrode active material is P2 ≥ 75% (satisfying both P2 ≥ 70% and P2 ≥ 60%). In most embodiments, P2 ≥ 80% is satisfied, and further P2 ≥ 90% is satisfied. In some embodiments, P2 exceeds 95%;

[0485] (3) According to the statistical results, R L / W All satisfy R L / W ≤4, and all within 0.95≤R L / W ≤4, R L / W The average values ​​of R L / W The average value is in the range of 1.5 to 2.0;

[0486] (4) According to the statistical results, all meet R MI <R MO , that is, the inner layer R L / W The average value is lower than the outer R L / W Average value; each embodiment satisfies R MI <1.8 and R MO ≥1.8, most examples satisfy 1.3≤R MI <1.8 and 1.8≤R MO ≤2.3; each embodiment satisfies the R L / W In the range of 1.2 to 4 and the inner layer RL / W At 0.95 ≤ R L / W ≤2.8; most embodiments satisfy the R of at least 80% of the primary particles in the outer layer L / W R in the range of 1.4 to 4 and at least 80% of the primary particles in the inner layer L / W In the range of 0.95 to 2.0;

[0487] (5) According to the statistical results, the anisotropic index of the angle α1 satisfies 0.4≤I α1 ≤2.5, most embodiments meet 0.5≤I α1 ≤2.0;

[0488] (6) D of positive electrode active material v 50 is 8 μm to 11 μm, at least 80% of the primary particles in the oriented secondary particles have a diameter in the range of 100 nm to 1600 nm, and the positive electrode active material satisfies 1.1≤SPAN≤1.4; some embodiments satisfy D v 50 is 9 μm to 11 μm, at least 80% of the primary particles in the oriented secondary particles have a diameter in the range of 400 nm to 1500 nm, and the positive electrode active material has 1.2≤SPAN≤1.3;

[0489] (7) According to statistical results, the positive electrode active material meets 15μm≤D v 90≤18μm, 4μm≤D v 10≤6μm, D n 10≥2μm; some embodiments further satisfy 16μm≤D v 90≤17μm, 4.5μm≤D v 10≤5.5μm.

[0490] Taking Example 1 as an example, according to Figure 2 The statistical results of the L value, W index and the direction of α1 deviation from the corresponding longitudinal direction of the primary particles in the inner and outer layers of one of the oriented secondary particles are shown in Table 2. The following information can be obtained: R L / W All in the range of 0.95~4, R L / W The average value is 1.86, R MI 1.51μm, R MO is 2.05μm, satisfying R MI <R MO ; R in the outer layer L / W The number of primary particles in the range of 1.4 to 4 accounts for about 81%, and the R L / W The number of primary particles in the range of 0.95 to 2.0 accounts for about 83%;

[0491] The L average value of the inner layer is less than 700nm, the L average value of the outer layer is 783.5nm (satisfying greater than or equal to 720nm and also satisfying greater than or equal to 750nm), the L average value of the inner layer is 649.4nm (satisfying less than or equal to 700nm and also satisfying less than or equal to 660nm), I α1 About 1.75.

[0492] Table 2.

[0493]

[0494] In Table 2: “α1 deviates from the corresponding longitudinal direction column”, “+” corresponds to the clockwise direction, “-” corresponds to the counterclockwise direction, and “other” indicates that the angle is not within the range of 15° to 45°.

[0495] The positive electrode active materials prepared in Examples 1-6 all have relatively high compaction densities, as shown in Table 3.

[0496] The lithium ion solid phase diffusion coefficient (25°C) of the positive electrode active materials prepared in Examples 1-6 is within 1×10 -9 cm 2 ·s -1 Up to 8×10 -9 cm 2 ·s - 1, wherein in Example 1 it is 2.5×10 -9 cm 2 ·s -1 Comparative Example 1 and Comparative Example 2 are both at 1×10 -9 cm 2 ·s -1 Below, where Comparative Example 1 is 5.2×10 -10 cm 2 ·s -1 , in Comparative Example 2, it is 1.8×10 -10 cm 2 ·s -1 Please refer to Table 3.

[0497] The secondary batteries prepared in Examples 1-6 all have high energy density, good kinetic performance and long cycle life.

[0498] In the positive electrode active material prepared in Comparative Example 1, F1 is relatively low; in the positive electrode active material prepared in Comparative Example 2, there are almost no oriented secondary particles, and according to the test results, α1 is less than 10°, which shows that the primary particles are mainly distributed along the radial direction of the secondary particles. The kinetic performance, energy density and cycle performance of the secondary batteries prepared in Comparative Examples 1 and 2 are all reduced to varying degrees.

[0499] Some test analysis results of some embodiments are summarized in Table 3.

[0500] Table 3.

[0501]

[0502] In Table 3, the compacted density of the powder at 4T was tested using an electronic pressure testing machine.

[0503] The description of each embodiment and example above tends to emphasize the differences between each embodiment and example, and the same or similar parts can be referenced to each other. For the sake of brevity, this article will not repeat them. The technical features of the above-described embodiments and examples can be combined arbitrarily. For the sake of brevity, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0504] It should be noted that the present application is not limited to the above-mentioned embodiments and examples. The above-mentioned embodiments and examples are only examples. Within the scope of the technical solution of the present application, the embodiments and examples that have the same structure as the technical idea and play the same effect are all included in the technical scope of the present application. The above-described embodiments and examples only express several embodiments and examples of the present application, and the description is relatively detailed, but it cannot be understood as a limitation on the scope of the patent. In addition, without departing from the scope of the subject matter of the present application, various modifications that can be thought of by a person skilled in the art to the embodiments or examples, and other methods of combining some of the constituent elements in the embodiments or examples are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: A positive electrode sheet is included, wherein the positive electrode sheet includes a positive electrode active material, wherein the positive electrode active material includes secondary particles, wherein the secondary particles are aggregates including a plurality of primary particles; and the primary particles include a positive electrode active substance; In any of the secondary particles, the direction from the center of the secondary particle toward the surface is recorded as the X direction; the X direction passing through the center of any of the primary particles is recorded as the longitudinal direction; in any of the primary particles, the longest axis of the primary particle is recorded as the a-axis; The secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, wherein 15°≤α1≤45°, and F1≥60%.

2. The secondary battery according to claim 1, characterized in that: The angle α1 is obtained in the following manner: in a cross section passing through the center of the oriented secondary particle, the direction from the center of the oriented secondary particle toward the surface of the oriented secondary particle is the X direction; the X direction passing through the center of the cross section of the primary particle is the longitudinal direction corresponding to the primary particle; the longest axis in the cross section of the primary particle is recorded as the a-axis; and the angle α1 is obtained based on the angle formed by the a-axis and the corresponding longitudinal direction.

3. The secondary battery according to claim 1 or 2, characterized in that: F1≥64%。 4. The secondary battery according to any one of claims 1 to 3, characterized in that The proportion of the oriented secondary particles in the secondary particles is recorded as P2, and P2≥60%.

5. The secondary battery according to claim 4, characterized in that: P2≥75%。 6. The secondary battery according to any one of claims 1 to 5, characterized in that: The length of the primary particle along the longitudinal direction is recorded as L, the length of the primary particle along the direction perpendicular to the longitudinal direction is recorded as W, and the ratio of L to W in the primary particle is recorded as R L / W ; In the oriented secondary particles, the R L / W Less than or equal to 4.

7. The secondary battery according to claim 6, characterized in that: The L value, the W value and the R L / W The value is obtained as follows: in a cross section passing through the center of the oriented secondary particle, the direction from the center of the oriented secondary particle toward the surface of the oriented secondary particle is the X direction; the X direction passing through the center of the cross section of the primary particle is the longitudinal direction corresponding to the primary particle; the L value is obtained according to the length value of the primary particle along the corresponding longitudinal direction, the W value is obtained according to the length value of the primary particle along the direction perpendicular to the corresponding longitudinal direction, and the R value is obtained according to the ratio obtained by dividing the L value by the W value. L / W value.

8. The secondary battery according to claim 6 or 7, characterized in that: The positive electrode active material satisfies at least one of the following characteristics: In the oriented secondary particles, the R L / W Satisfy 0 <R L / W ≤4; In the oriented secondary particles, the R L / W The average value is 1.5 to 2.

5.

9. The secondary battery according to any one of claims 6 to 8, characterized in that The positive electrode active material satisfies at least one of the following characteristics: In the oriented secondary particles, the R L / W Satisfy 0.95≤R L / W ≤4; In the oriented secondary particles, the R L / W The average value is 1.5~2.

0.

10. The secondary battery according to any one of claims 6 to 9, characterized in that The distance from the center to the surface of the oriented secondary particle is recorded as R; the portion from the center of the oriented secondary particle to the position 2 / 3R from the center is recorded as the inner layer, and the portion from the position 2 / 3R from the center to the surface of the oriented secondary particle is recorded as the outer layer; In the oriented secondary particles, the R L / W The average value is recorded as R MI , the outer layer R L / W The average value is recorded as R MO , where R MI <R MO .

11. The secondary battery according to claim 10, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: In the oriented secondary particles, R MI <1.8, R MO ≥1.8; In the oriented secondary particles, the R L / W Satisfy 1.2≤R L / W ≤4, the inner layer R L / W Satisfy 0.95≤R L / W ≤2.

8.

12. The secondary battery according to claim 10 or 11, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: In the oriented secondary particles, 1.3≤R MI <1.8, 1.8≤R MO ≤2.3; In the oriented secondary particles, at least 80% of the primary particles in the outer layer have R L / W Satisfy 1.4≤R L / W ≤4, at least 80% of the primary particles in the inner layer have R L / W Satisfy 0.95≤R L / W ≤2.

0.

13. The secondary battery according to any one of claims 6 to 12, characterized in that: In the oriented secondary particles, the R L / W The value increases from the center of the oriented secondary particle to the surface of the oriented secondary particle.

14. The secondary battery according to any one of claims 1 to 13, characterized in that: The number of primary particles whose a-axis in the oriented secondary particles forms an angle α1 with the longitudinal direction is counted, and the anisotropic index of the angle α1 is recorded as I α1 , then 0.4≤I α1 ≤2.5; Wherein, in the cross section passing through the center of the oriented secondary particle, the angle α1 that the a-axis deviates from the corresponding longitudinal direction in the clockwise direction is recorded as a positive angle, and the angle α1 that the a-axis deviates from the corresponding longitudinal direction in the counterclockwise direction is recorded as a negative angle, I α1 It is the ratio of the number of positive angles to the number of negative angles.

15. The secondary battery according to claim 14, characterized in that: 0.5≤I α1 ≤2.0。 16. The secondary battery according to any one of claims 1 to 14, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: The positive electrode active material D v 50: 8μm~11μm; The diameter of at least 80% of the primary particles in the oriented secondary particles is in the range of 100 nm to 1600 nm, wherein the diameter of the primary particles refers to the maximum length of the primary particles in each direction; The particle size distribution parameter SPAN of the positive electrode active material conforms to the following formula: SPAN = (D v 90-D v 10) / D v 50, among which, 1.1≤SPAN≤1.

4.

17. The secondary battery according to claim 16, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: The positive electrode active material D v 50: 9μm~11μm; The diameter of at least 80% of the primary particles in the oriented secondary particles is within the range of 400nm to 1500nm; The SPAN of the positive electrode active material satisfies: 1.2≤SPAN≤1.

3.

18. The secondary battery according to claims 1 to 17, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: The positive electrode active material D v 90Satisfy: 15μm≤D v 90≤18μm; The positive electrode active material D v 10: 4μm≤D v 10≤6μm; The positive electrode active material D n 10 Satisfied: D n 10≥2μm.

19. The secondary battery according to claim 18, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: The positive electrode active material D v 90 satisfies: 16μm≤D v 90≤17μm; The positive electrode active material D v 10: 4.5μm≤D v 10≤5.5μm.

20. The secondary battery according to any one of claims 1 to 19, characterized in that: In the oriented secondary particles, the positive electrode active material includes a layered lithium ion active material.

21. The secondary battery according to any one of claims 1 to 20, characterized in that: In the oriented secondary particles, the positive electrode active material includes a lithium-containing nickel composite oxide.

22. The secondary battery according to claim 21, characterized in that: The molar ratio of nickel element to oxygen element in the lithium-containing nickel composite oxide is denoted as Q Ni / O , where 0.3≤Q Ni / O ≤0.

5.

23. The secondary battery according to claim 21 or 22, characterized in that: The oriented secondary particles satisfy one or more of the following characteristics: In the oriented secondary particles, 0.4≤Q Ni / O ≤0.5; The lithium-containing nickel composite oxide contains at least one of a Co element and an M element, wherein the M element is at least one of a Mn element and an Al element; The lithium-nickel composite oxide contains a doping element, Q Ni / O <0.5, the doping element includes at least one element selected from Zr, Al, B, Sr and Ca; At least a portion of the primary particles include a particle body and a coating layer located at least a portion of the surface of the particle body, the particle body includes a lithium-nickel composite oxide, and the coating layer includes at least one element of Zr, Al, B, Sr and Ca.

24. The secondary battery according to any one of claims 21 to 23, characterized in that: In the oriented secondary particles, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and any modified form of the foregoing substances, wherein the modified form includes one or more of doping modification and coating modification, the doping element used for the doping modification includes at least one of Zr, Al, B, Sr and Ca, and the coating element used for the coating modification includes at least one of Zr, Al, B, Sr and Ca; The molar ratio R of the nickel element to the oxygen element in the positive electrode active material is Ni / O Satisfy 0.4≤R Ni / O ≤0.

5.

25. The secondary battery according to claim 24, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: The positive electrode active material D v 50: 8μm~11μm; At least 80% of the primary particles in the oriented secondary particles have a diameter in the range of 100 nm to 1600 nm; The particle size distribution parameter SPAN of the positive electrode active material conforms to the following formula: SPAN = (D v 90-D v 10) / D v 50, among which, 1.1≤SPAN≤1.

4.

26. The secondary battery according to claim 25, characterized in that: The positive electrode active material satisfies one or more of the following characteristics: The positive electrode active material D v 50: 9μm~10μm; The diameter of at least 80% of the primary particles in the oriented secondary particles is within the range of 400nm to 1500nm; The SPAN of the positive electrode active material satisfies: 1.2≤SPAN≤1.

3.

27. The secondary battery according to any one of claims 24 to 26, characterized in that: In the oriented secondary particles, the average L value of the inner layer is less than 700 nm, and the average L value of the outer layer is greater than or equal to 720 nm; Among them, the length value of the primary particle along the longitudinal direction is recorded as L, and the distance from the center to the surface of the oriented secondary particle is recorded as R; the part from the center of the oriented secondary particle to the position 2 / 3R from the center is recorded as the inner layer, and the part from the position 2 / 3R from the center to the surface of the oriented secondary particle is recorded as the outer layer.

28. The secondary battery according to claim 27, characterized in that: In the oriented secondary particles, an average L value of the inner layer is less than or equal to 660 nm, and an average L value of the outer layer is greater than or equal to 750 nm.

29. The secondary battery according to any one of claims 1 to 28, characterized in that: The secondary battery further comprises a negative electrode sheet, a separator and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.

30. The secondary battery according to any one of claims 1 to 29, characterized in that: The secondary battery is a lithium ion secondary battery.

31. A positive electrode active material, characterized in that The positive electrode active material includes secondary particles, wherein the secondary particles are aggregates including a plurality of primary particles; the primary particles include a positive electrode active material; In any of the primary particles, the longest axis of the primary particle is recorded as the a-axis; in any of the secondary particles, the direction from the center of the secondary particle toward the surface is recorded as the X direction; the X direction passing through the center of any of the primary particles is recorded as the longitudinal direction; The secondary particles include oriented secondary particles; in the oriented secondary particles, based on the total number of primary particles in the oriented secondary particles, the proportion of primary particles whose a-axis forms an angle α1 with the longitudinal direction in the oriented secondary particles is recorded as F1, wherein 15°≤α1≤45°, and F1≥60%.

32. The positive electrode active material according to claim 31, characterized in that The positive electrode active material in the secondary battery according to any one of claims 2 to 28.

33. An electrical device, characterized in that: The secondary battery comprises at least one of the secondary battery according to any one of claims 1 to 30 and the positive electrode active material according to claim 31 or 32.

Citation Information

Patent Citations

  • Positive electrode active material and lithium secondary battery including the same

    CN112397708A

  • Ternary material, preparation method and battery

    CN113363497A

  • Positive electrode material, secondary battery, and electric device

    CN118173773A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, and method for producing the same

    JP2016167439A

Cited By

  • Secondary battery, active cathode material and power-consuming device

    DE212025000080U1

  • Secondary battery, positive electrode active material, and electric device

    EP4760847A1

  • Secondary battery, positive electrode active material, and electric device

    WO2026011960A1